A low-alkaline condition flotation reagent composition and use thereof
Patent Information
- Application Number
- CN202611424068.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-15
- Publication Date
- 2026-10-16
AI Technical Summary
[0007]本发明的目的在于提供一种低碱条件的浮选药剂组合物及其应用,以解决铅锌金银硫化矿选铅作业中闪锌矿和黄铁矿抑制程度波动,以及铅矿物回收与锌、硫进入铅精矿之间难以协调的问题
[0047] 1) Sodium carboxymethyl lignin undergoes 5 kDa ultrafiltration pre-fractionation, two-stage carboxymethylation, and 3 kDa ultrafiltration washing to ensure that newly added carboxymethyl groups are mainly retained in the high-molecular-weight lignin sulfonate segments, while reducing the residue of low-molecular-weight reactants and byproducts. The carboxyl groups form multi-site coordination with zinc and iron sites on the surface of sphalerite and pyrite, while the sulfonic acid groups maintain the hydration and extension of the high-molecular-weight segments. Zinc sulfate and sodium sulfite are compounded according to the prescribed effective component mass ratio, allowing hydrated or hydroxylated zinc species and sulfite ions to jointly regulate the chemical state of the sphalerite and pyrite surfaces, and together with the high-molecular-weight adsorption layer formed by sodium carboxymethyl lignin, constitute the interfacial hydration layer. This hydration layer restricts the adsorption of sulfur-containing collectors on the surface of sphalerite and pyrite, maintaining the flotation difference between lead minerals and zinc and iron sulfide minerals under pH conditions of 7.8–8.8.
Smart Images

Figure CN122913000A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of mineral flotation technology, specifically relating to a flotation reagent composition under low-alkali conditions and its application. Background Technology
[0002] Lead-zinc-gold-silver sulfide ores typically contain galena, sphalerite, and pyrite. Gold and silver occur as fine particles, lattice components, or inclusions within these sulfide minerals. In beneficiation, galena is usually floated first, followed by the recovery of sphalerite and pyrite from the lead tailings. The lead beneficiation stage must ensure lead recovery while minimizing the amount of sphalerite and pyrite entering the lead concentrate, while also considering the recovery of associated gold and silver.
[0003] Traditional lead beneficiation processes often use lime and zinc sulfate to suppress pyrite and sphalerite, and employ No. 25 black reagent to collect galena. When a large amount of lime is used, the alkalinity of the pulp increases, suppressing pyrite and making it difficult for some gold associated with or contained within pyrite to enter the lead concentrate. No. 25 black reagent has poor dispersibility in water and has an irritating odor, limiting the preparation and on-site application of the reagent. Therefore, lead beneficiation processes have begun to use low-alkali modifiers and water-soluble lead collectors to replace lime, zinc sulfate, and No. 25 black reagent.
[0004] Using HQD82 to condition the pulp and adding HQ77 to collect galena allows for lead-zinc separation at lower alkalinity and reduces the zinc content in the lead concentrate. However, the oxidation level of lead-zinc ore, mineral intergrowth, and pulp ionic composition vary with ore batches and circulating water conditions. Newly formed mineral surfaces from grinding and metal ions in the pulp alter the surface state of sphalerite and pyrite, causing them to adsorb lead collectors and enter the lead concentrate. Relying solely on the pretreatment agents added at the beginning is insufficient to continuously process the mineral surfaces re-exposed during roughing and cleaning, leading to fluctuations in the zinc and sulfur content of the lead concentrate.
[0005] Increasing the amount of modifier can enhance the inhibition of sphalerite and pyrite, but it also increases the proportion of the modifier in contact with the galena surface, thus inhibiting galena and its associated gold and silver minerals. Existing reagent systems are insufficient to simultaneously control the zinc and sulfur content in lead concentrate while maintaining the recovery of lead, gold, and silver, and lack interface conditioning measures corresponding to different flotation stages.
[0006] Therefore, there is a need for a flotation reagent composition under low-alkali conditions and its application, which can, while maintaining the galena collection process, stage-wise regulate the surface of sphalerite and pyrite, reduce the entry of sphalerite and pyrite into lead concentrate, and control the impact of the reagent on the recovery process of lead, gold and silver. Summary of the Invention
[0007] The purpose of this invention is to provide a flotation reagent composition under low-alkali conditions and its application, in order to solve the problems of fluctuations in the inhibition of sphalerite and pyrite in lead beneficiation of lead-zinc-gold-silver sulfide ores, and the difficulty in coordinating lead ore recovery with the entry of zinc and sulfur into lead concentrate.
[0008] To achieve the above objectives, according to one aspect of the present invention, a flotation reagent composition for low-alkali conditions is provided, comprising separately packaged sodium carboxymethyl lignin, a zinc salt-sulfite complex, a dialkyl dithiophosphate, a terpene alcohol mixture, and an ethyl xanthate-butyl xanthate complex. With 100 parts by weight of sodium carboxymethyl lignin on a dry basis, and the remaining components by weight of active ingredient, the flotation reagent composition comprises 100 parts of sodium carboxymethyl lignin, 1250–3340 parts of the zinc salt-sulfite complex, 125–385 parts of the dialkyl dithiophosphate, 13–40 parts of the terpene alcohol mixture, and 6–34 parts of the ethyl xanthate-butyl xanthate complex.
[0009] In the zinc salt-sulfite compound, the mass ratio of zinc salt to sulfite, based on the mass of active ingredients, is (1.0-2.0):1. In the ethyl xanthate-butyl xanthate compound, the mass ratio of ethyl xanthate to butyl xanthate, based on the mass of active ingredients, is 1:(1.0-2.0).
[0010] Preferably, the zinc salt-sulfite complex is composed of zinc sulfate and sodium sulfite. The effective component of the zinc sulfate is calculated as ZnSO4 by mass, and the effective component of the sodium sulfite is calculated as Na2SO3 by mass.
[0011] Preferably, the mass ratio of zinc sulfate to sodium sulfite, based on the mass of the effective components, is 3:2.
[0012] Preferably, the dialkyl dithiophosphate is selected from at least one of diethyl dithiophosphate, dipropyl dithiophosphate, diisopropyl dithiophosphate, dibutyl dithiophosphate, and diisobutyl dithiophosphate.
[0013] Preferably, the terpene alcohol mixture includes terpineol.
[0014] Preferably, the ethyl xanthate-butyl xanthate complex is composed of an alkali metal salt of ethyl xanthate and an alkali metal salt of butyl xanthate.
[0015] Preferably, the mass ratio of the ethyl xanthate alkali metal salt to the butyl xanthate alkali metal salt, based on the mass of the effective components, is 2:3.
[0016] Preferably, the flotation reagent composition comprises 100 parts by weight of sodium carboxymethyl lignin on a dry basis, 1660-2500 parts by weight of zinc salt-sulfite compound, 190-250 parts by weight of dialkyl dithiophosphate, 20-27 parts by weight of terpene alcohol mixture, and 11-17 parts by weight of ethyl xanthate-butyl xanthate compound, based on the dry basis of 100 parts by weight of the remaining components according to the mass of the effective ingredients.
[0017] The carboxymethyl lignin sodium is a pre-fractionated two-stage carboxymethylated lignin sulfonate sodium, and its preparation method includes the following steps:
[0018] P1. Add sodium lignosulfonate to water to prepare an aqueous solution of sodium lignosulfonate, stir and then filter.
[0019] P2, the sodium lignosulfonate aqueous solution obtained in step P1 is washed and concentrated through an ultrafiltration membrane with a nominal molecular weight cutoff of 5 kDa, and the retentate is collected;
[0020] P3, add the first portion of sodium hydroxide to the retentate obtained in step P2 for alkalization treatment;
[0021] P4. Add 65-75% of the total amount of sodium chloroacetate to the material obtained in step P3 to carry out the first stage of carboxymethylation reaction.
[0022] P5. Heat the material obtained in step P4, add the remaining 25-35% sodium chloroacetate and the second part of sodium hydroxide dropwise to carry out the second stage of carboxymethylation reaction.
[0023] P6. Cool the reaction solution obtained in step P5, add hydrochloric acid to adjust the pH, wash and filter it through an ultrafiltration membrane with a nominal molecular weight cutoff of 3 kDa, and collect the retentate.
[0024] P7. Concentrate the retentate obtained in step P6 to obtain the carboxymethyl lignosulfonate.
[0025] Preferably, based on 100 parts by weight (dry basis) of the sodium lignosulfonate residue obtained in step P2, the raw materials for preparing the carboxymethyl lignosulfonate include 100 parts of the sodium lignosulfonate residue, 32-44 parts of sodium chloroacetate, 11.8-17.9 parts of sodium hydroxide, and 550-750 parts of water for reaction preparation. The washing and filtration water used in steps P2 and P6 is calculated separately. The amount of hydrochloric acid added is sufficient to adjust the pH of the reaction solution obtained in step P5 to 7.8-8.3.
[0026] Preferably, in step P1, the solid content of the sodium lignosulfonate aqueous solution is 12-18 wt%, the stirring temperature is 25-35℃, and the stirring time is 30-60 min.
[0027] Preferably, in step P2, the ultrafiltration temperature is 25–35°C, the transmembrane pressure difference is 0.15–0.30 MPa, the volume of washing water is 3–4 times the initial volume of the retentate, and the solid content of the resulting retentate is 15–20 wt%.
[0028] Preferably, in step P3, the alkalization treatment temperature is 30–34°C, the pH is 11.8–12.2, and the alkalization time is 20–40 min.
[0029] Preferably, in step P4, the sodium chloroacetate is added over a period of 60–90 min, the reaction temperature is 36–40 °C, the pH is 11.6–12.0, and the reaction time after the addition is complete is 30–45 min.
[0030] Preferably, in step P5, the heating rate of the material is 0.2-0.5℃ / min, the sodium chloroacetate is added dropwise for 30-60 min, the reaction temperature is 46-50℃, the pH is 11.1-11.5, and the reaction time after the addition is 2-3 h; the ratio of the total amount of sodium hydroxide in the first part and the second part to the total amount of sodium chloroacetate is 1.08-1.18:1.
[0031] Preferably, in step P6, the reaction solution obtained in step P5 is cooled to no higher than 30°C and then pH is adjusted; the ultrafiltration temperature is 25-35°C, the transmembrane pressure difference is 0.15-0.30 MPa, and the volume of washing water is 4-6 times the initial volume of the retentate.
[0032] Preferably, based on 100 parts by weight of the sodium lignosulfonate residue obtained in step P2 (dry basis), the amount of sodium chloroacetate added is 38 parts, and the amount of sodium hydroxide added is 14.75 parts; 70% of the total amount of sodium chloroacetate is added in step P4, and the remaining 30% of sodium chloroacetate is added in step P5; the ratio of the total amount of sodium hydroxide to the total amount of sodium chloroacetate is 1.13:1.
[0033] Preferably, the carboxyl group increment of the sodium carboxymethyl lignin relative to the sodium lignin sulfonate residue obtained in step P2 is 0.50–0.70 mmol / g dry basis, the sulfonic acid group content is 1.40–1.80 mmol / g dry basis, and the molar ratio of the carboxyl group increment to the sulfonic acid group content is 0.30–0.45:1.
[0034] Preferably, in the aqueous size exclusion chromatogram of the carboxymethyl lignin sodium, the percentage of the peak area with a molecular weight less than 3000 Da is no more than 5% of the total peak area; the solid content of the carboxymethyl lignin sodium is 18-22 wt%, and the pH is 7.8-8.3.
[0035] According to another aspect of the present invention, the application of the above-described low-alkali flotation reagent composition in the flotation of lead-zinc-gold-silver sulfide ores is provided. The zinc salt-sulfite complex is composed of zinc sulfate and sodium sulfite, wherein the mass ratio of zinc sulfate to sodium sulfite, based on the effective components, is (1.0–2.0):1; the ethyl xanthate-butyl xanthate complex is composed of ethyl xanthate alkali metal salt and butyl xanthate alkali metal salt, wherein the mass ratio of ethyl xanthate alkali metal salt to butyl xanthate alkali metal salt, based on the effective components, is 1:(1.0–2.0). The application includes the following steps:
[0036] M1, grinding lead-zinc-gold-silver sulfide ore to obtain slurry for flotation;
[0037] M2, add zinc salt-sulfite compound to the slurry to be flotated obtained in step M1, adjust the pH of the slurry to 7.8-8.8 and perform slurry conditioning;
[0038] M3, add dihydrodithiophosphate to the slurry obtained in step M2 and stir;
[0039] M4, add 70-80% of the total amount of sodium carboxymethyl lignosulfonate to the slurry obtained in step M3 and stir;
[0040] M5, add a mixture of terpene alcohols to the slurry obtained in step M4, and perform aeration roughing to obtain roughing concentrate and roughing tailings respectively;
[0041] M6. Add the remaining 20-30% of sodium carboxymethyl lignosulfonate to the rough concentrate obtained in step M5 and stir to carry out fine selection, and obtain lead concentrate and fine tailings. Return the fine tailings obtained to the roughing operation.
[0042] M7. Add ethyl xanthate-butyl xanthate complex to the roughing tailings obtained in step M5 and stir. Perform scavenging to obtain scavenged concentrate and flotation tailings. Return the obtained scavenged concentrate to the roughing operation.
[0043] Preferably, the total amount of carboxymethyl lignosulfonate added on a dry basis is 30-60 g / t of raw ore; the amounts of zinc salt-sulfite complex, dialkyl dithiophosphate, terpene alcohol mixture, and ethyl xanthate-butyl xanthate complex added, based on the effective ingredients, are 750-1000 g / t of raw ore, 75-115 g / t of raw ore, 8-12 g / t of raw ore, and 4-10 g / t of raw ore, respectively.
[0044] Preferably, in step M1, the grinding fineness is such that mineral particles with a diameter less than 0.074 mm account for 70-80% of the total mass of mineral particles, the slurry solids concentration is 35-42%, and the slurry temperature is 10-35℃.
[0045] Preferably, in step M2, the slurry conditioning time after adding the zinc salt-sulfite compound is 180 s; in step M3, the stirring time after adding dialkyl dithiophosphate is 120-180 s; in step M4, the stirring time after adding the first portion of carboxymethyl lignosulfonate is 60-120 s; in step M5, the stirring time after adding the terpene alcohol mixture is 30-60 s, and the coarse selection time is 4 min; in step M6, the stirring time after adding the remaining carboxymethyl lignosulfonate is 90-150 s, and the fine selection time is 3 min; in step M7, the stirring time after adding the ethyl xanthate-butyl xanthate compound is 60 s, and the scavenging time is 8 min.
[0046] Compared with the prior art, the beneficial effects of the present invention are:
[0047] 1) Sodium carboxymethyl lignin undergoes 5 kDa ultrafiltration pre-fractionation, two-stage carboxymethylation, and 3 kDa ultrafiltration washing to ensure that newly added carboxymethyl groups are mainly retained in the high-molecular-weight lignin sulfonate segments, while reducing the residue of low-molecular-weight reactants and byproducts. The carboxyl groups form multi-site coordination with zinc and iron sites on the surface of sphalerite and pyrite, while the sulfonic acid groups maintain the hydration and extension of the high-molecular-weight segments. Zinc sulfate and sodium sulfite are compounded according to the prescribed effective component mass ratio, allowing hydrated or hydroxylated zinc species and sulfite ions to jointly regulate the chemical state of the sphalerite and pyrite surfaces, and together with the high-molecular-weight adsorption layer formed by sodium carboxymethyl lignin, constitute the interfacial hydration layer. This hydration layer restricts the adsorption of sulfur-containing collectors on the surface of sphalerite and pyrite, maintaining the flotation difference between lead minerals and zinc and iron sulfide minerals under pH conditions of 7.8–8.8.
[0048] 2) Dihydrodithiophosphate first binds to the lead sites on the surface of galena, forming a collector adsorption layer. Subsequently added carboxymethyl lignosulfonate mainly contacts the surfaces of sphalerite and pyrite not covered by the collector. A mixture of terpene alcohols is distributed at the gas-liquid interface, maintaining the froth layer in the roughing stage. Ethyl xanthate alkali metal salts and butyl xanthate alkali metal salts are added to the scavenging pulp according to the specified effective component mass ratio. Short-chain and long-chain xanthates work together to react with the remaining galena and lead-bearing intergrowth particles in the roughing tailings. The front-stage dithiophosphate collector and the rear-stage xanthate collector are interconnected, maintaining lead-zinc separation selectivity in the roughing stage and recovering lead minerals and associated gold and silver components that did not enter the roughing concentrate during the scavenging stage.
[0049] 3) 70-80% of the total sodium carboxymethyl lignosulfonate is added before roughing to build an initial adsorption hydration layer on the surface of newly formed sphalerite and pyrite formed during grinding; the remaining 20-30% is added before cleaning to supplement and cover zinc and iron sites that are re-exposed during roughing due to particle collision, surface abrasion, and changes in pulp chemistry. Cleaning tailings and scavenging concentrate are returned to the roughing operation, allowing the returned material to re-enter the pulp conditioning, collecting, and interface adjustment processes, reducing the proportion of zinc minerals and pyrite entering the lead concentrate, and maintaining the recovery rate of lead and associated gold and silver components in the low-alkali flotation process. Attached Figure Description
[0050] Figure 1 Fourier transform infrared spectra of sodium lignosulfonate raw material, 5 kDa pre-fractionated residue, and carboxymethyl sodium lignosulfonate prepared in Example 1. Curve a represents sodium lignosulfonate raw material, curve b represents the 5 kDa pre-fractionated residue, and curve c represents carboxymethyl sodium lignosulfonate prepared in Example 1. To distinguish the spectra of different samples, curves a, b, and c are shifted along the vertical axis; the vertical position does not represent the absolute absorbance difference between different samples.
[0051] Figure 2 This figure shows the aqueous size exclusion chromatograms of sodium lignosulfonate raw material, single-stage carboxymethylated sodium lignosulfonate prepared in Comparative Example 3, and carboxymethyl sodium lignosulfonate prepared in Example 1. Curve a represents sodium lignosulfonate raw material, curve b represents single-stage carboxymethylated sodium lignosulfonate prepared in Comparative Example 3, and curve c represents carboxymethyl sodium lignosulfonate prepared in Example 1. To distinguish the chromatograms of different samples, curves a, b, and c are shifted along the vertical axis. The vertical position does not represent the absolute difference in refractive response between different samples. The vertical dashed line in the figure represents the retention time corresponding to an apparent molecular weight of 3000 Da relative to the sodium polystyrene sulfonate standard. The region to the right of the vertical dashed line represents the response region of polymers with an apparent molecular weight less than 3000 Da. Detailed Implementation
[0052] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are preferred embodiments of the present invention and should not be considered as excluding other embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0053] In the claims and description of this invention, the terms "comprising," "having," and variations thereof are used to mean "including but not limited to."
[0054] For ease of explanation of the technical solution of this invention, the zinc salt-sulfite complex is represented by the trade code HQD82 in this specification. HQD82 is composed of zinc sulfate and sodium sulfite, and the mass ratio of zinc sulfate to sodium sulfite based on the effective component mass is (1.0~2.0):1, preferably 3:2. The effective component mass of zinc sulfate is calculated as ZnSO4, and the effective component mass of sodium sulfite is calculated as Na2SO3. The dialkyl dithiophosphate is represented by the trade code HQ77, which includes diethyl dithiophosphate. At least one of phosphate, dipropyl dithiophosphate, diisopropyl dithiophosphate, dibutyl dithiophosphate, and diisobutyl dithiophosphate; terpene alcohol mixtures are indicated as No. 2 oil, which includes terpineol; ethyl xanthate-butyl xanthate complexes are indicated as butyl xanthate, which consists of ethyl xanthate alkali metal salt and butyl xanthate alkali metal salt, wherein the mass ratio of ethyl xanthate alkali metal salt to butyl xanthate alkali metal salt, based on the mass of the active ingredient, is 1:(1.0-2.0), preferably 2:3. The above designations are used to indicate the corresponding chemical composition and do not limit the manufacturer, source of goods, or batch of the reagent. Sodium carboxymethyl lignin is a pre-graded, two-stage carboxymethylated lignin sulfonate, formulated and packaged separately with HQD82, HQ77, No. 2 oil, and butyl xanthate.
[0055] The flotation reagent composition of this invention is packaged independently. Sodium carboxymethyl lignosulfonate, HQD82, HQ77, No. 2 oil, and butyl xanthate are separated during storage and transportation, and added to the pulp in a prescribed order during flotation. Separate packaging reduces the influence of inorganic ions in HQD82 on the hydration state and solution viscosity of sodium carboxymethyl lignosulfonate segments, and reduces the possibility of zinc ions coordinating with dithiophosphate and xanthate ions or forming insoluble compounds during storage, thus maintaining the dispersion and effective component concentration of each reagent before addition to the pulp.
[0056] Preparation principle of carboxymethyl lignosulfonate
[0057] Sodium lignin sulfonate raw materials are characterized by a wide molecular weight distribution, and the content of low-molecular-weight lignin fragments and water-soluble inorganic salts varies with the source of the raw material. Low-molecular-weight components diffuse rapidly, but the adsorption layer formed on the mineral surface is thin, making them prone to desorption during slurry stirring and particle collision. In the preparation of carboxymethyl lignin sodium, sodium lignin sulfonate is first prepared into an aqueous solution with a solid content of 12–18 wt%, stirred at 25–35℃ for 30–60 min, and then filtered. When the solid content is below 12 wt%, the sodium lignin sulfonate content per unit volume of solution decreases, increasing the load for subsequent ultrafiltration and concentration; when the solid content is above 18 wt%, the solution viscosity increases, and insufficiently dispersed lignin aggregates easily increase filtration resistance. 25–35℃ is favorable for the dissolution and chain segment expansion of sodium lignin sulfonate. When the stirring time is less than 30 min, the aggregates in the raw material are not easily dispersed sufficiently; after the stirring time exceeds 60 min, the effect of continued stirring on the dissolution and dispersion states decreases.
[0058] The filtered sodium lignin sulfonate aqueous solution was washed and concentrated through an ultrafiltration membrane with a nominal molecular weight cutoff of 5 kDa, and the retentate was collected. This pre-fractionation process removes some low-molecular-weight lignin fragments and water-soluble inorganic salts, allowing the subsequent carboxymethylation reaction to mainly occur on high-molecular-weight lignin sulfonate segments with multiple reactive hydroxyl sites. The ultrafiltration temperature was controlled at 25–35 °C. Below 25 °C, the solution viscosity increased and the membrane flux decreased; above 35 °C, concentration polarization at the membrane surface accelerated, and fractionation stability decreased. The transmembrane pressure difference was controlled at 0.15–0.30 MPa. Below 0.15 MPa, the permeate flux was insufficient; above 0.30 MPa, the filter cake layer on the membrane surface compacted, increasing the mass transfer resistance of low-molecular-weight substances. The volume of washing water was 3–4 times the initial volume of the retentate. When the volume of washing water is less than 3 times the volume of the filter, the removal of low molecular weight components and inorganic salts is insufficient; when it exceeds 4 times the volume, the effect of continued washing on the molecular weight distribution of the retentate decreases, and the subsequent concentration load increases. The solid content of the resulting retentate is controlled at 15–20 wt% to balance reactant concentration, material flowability, and mass transfer uniformity during the dropping process.
[0059] Based on 100 parts by weight of the pre-fractionated sodium lignosulfonate residue (dry basis), add 32–44 parts sodium chloroacetate, 11.8–17.9 parts sodium hydroxide, and 550–750 parts water for reaction preparation. When the water content in the reaction preparation is less than 550 parts, the material viscosity increases, and a local concentration gradient easily forms in the sodium chloroacetate droplet area; when the water content exceeds 750 parts, the reactant concentration decreases, and the carboxymethylation reaction rate decreases. When the sodium chloroacetate content is less than 32 parts, the number of carboxymethyl groups available for introduction decreases, making it difficult to control the carboxyl group increment within the specified range; when the sodium chloroacetate content exceeds 44 parts, the content of unreacted sodium chloroacetate and its hydrolysis products increases, and the subsequent ultrafiltration washing load is increased. The amount of sodium hydroxide added is determined based on the amount of sodium chloroacetate added, ensuring that the ratio of the total amount of sodium hydroxide to the total amount of sodium chloroacetate is 1.08–1.18:1.
[0060] The alkalization treatment employed a staged addition of sodium hydroxide. The first portion of sodium hydroxide was added to the pre-fractionated retentate, and alkalization was carried out for 20–40 min at 30–34 °C and pH 11.8–12.2. Hydroxide ions promoted the conversion of phenolic hydroxyl groups and some aliphatic hydroxyl groups in the lignin chains into more nucleophilic oxygen-containing groups, providing reaction sites for their substitution reaction with sodium chloroacetate. When the temperature was below 30 °C or the alkalization time was less than 20 min, the lignin chain extension and hydroxyl activation were insufficient; when the temperature was above 34 °C or the alkalization time exceeded 40 min, the increase in the number of active sites tended to stabilize, while the proportion of side reactions increased under alkaline conditions. Below pH 11.8, the degree of hydroxyl activation decreased; above pH 12.2, the subsequently added sodium chloroacetate was more prone to hydrolysis.
[0061] In the first stage of the carboxymethylation reaction, 65-75% of the total sodium chloroacetate is added, preferably 70%. Sodium chloroacetate is added dropwise over 60-90 minutes, with the reaction temperature controlled at 36-40°C and the pH at 11.6-12.0. After the addition is complete, the reaction continues for another 30-45 minutes. This stage allows sodium chloroacetate to undergo nucleophilic substitution with sterically less hindered and more reactive oxygen-containing groups, forming ether-linked carboxymethyl groups on the lignin sulfonate chain. When the proportion added in the first stage is less than 65%, fewer carboxymethyl sites are formed in the first stage, increasing the reaction load in the second stage; when the proportion added in the first stage is greater than 75%, the local concentration of sodium chloroacetate increases in the initial stage of the reaction, reducing substitution uniformity and increasing hydrolysis consumption. When the dropwise addition time is less than 60 minutes, the local reactant concentration is high; when the dropwise addition time exceeds 90 minutes, the reaction time difference between successively added materials increases. 36-40°C can maintain the substitution reaction rate in the first stage and limit the hydrolysis of sodium chloroacetate. When the temperature is below 36℃, the rate of nucleophilic substitution reaction decreases; when the temperature is above 40℃, the proportion of sodium chloroacetate hydrolyzed increases.
[0062] After the first stage reaction is completed, the temperature is increased to 46–50°C at a rate of 0.2–0.5°C / min, while the remaining 25–35% of sodium chloroacetate and the second portion of sodium hydroxide are added dropwise. When the heating rate is below 0.2°C / min, the reaction period is prolonged, and the residence time of the added sodium chloroacetate in the alkaline aqueous phase increases; when the heating rate is above 0.5°C / min, a temperature gradient easily forms within the reaction system. In the second stage, sodium chloroacetate is added dropwise over 30–60 min, with the pH controlled at 11.1–11.5, and the reaction continues for 2–3 h after the addition is completed. Increasing the reaction temperature can increase the reaction rate of sterically hindered hydroxyl sites, while appropriately decreasing the pH can limit the hydrolysis of sodium chloroacetate under high-temperature alkaline conditions. When the temperature is below 46°C or the reaction time is less than 2 h, the second-stage substitution reaction is incomplete; when the temperature is above 50°C or the reaction time exceeds 3 h, the proportion of sodium chloroacetate hydrolysis and alkaline degradation of lignin segments increases. When the pH is below 11.1, the concentration of active oxygen-containing groups decreases; when the pH is above 11.5, hydrolysis side reactions under high temperature conditions increase.
[0063] The molar ratio of the total amount of sodium hydroxide to the total amount of sodium chloroacetate is controlled at 1.08–1.18:1. When this molar ratio is below 1.08:1, the system struggles to maintain the basicity required for hydroxyl activation and nucleophilic substitution; when it is above 1.18:1, excess hydroxide promotes the conversion of sodium chloroacetate to glycolate, reducing the proportion of sodium chloroacetate participating in the carboxymethylation reaction. Based on 100 parts by weight of the pre-fractionated sodium lignin sulfonate residue (dry basis), preferably 38 parts of sodium chloroacetate and 14.75 parts of sodium hydroxide are added, resulting in a molar ratio of total sodium hydroxide to total sodium chloroacetate of 1.13:1.
[0064] After the reaction is complete, the reaction solution is cooled to no higher than 30°C, and then hydrochloric acid is added to adjust the pH to 7.8–8.3. Neutralization after cooling controls the localized temperature rise caused by acid-base neutralization, reducing the shrinkage or aggregation of lignin sulfonate segments caused by localized high ionic strength. When the pH is higher than 8.3, the residual alkalinity of the carboxymethyl lignin sodium product increases; when the pH is lower than 7.8, the neutralized salt content increases, and the degree of dissociation of some carboxyl groups decreases. Controlling the pH at 7.8–8.3 keeps the carboxyl and sulfonic acid groups in an ionized state, maintaining the dispersibility of carboxymethyl lignin sodium in the aqueous phase.
[0065] The neutralized reaction solution was washed through an ultrafiltration membrane with a nominal molecular weight cutoff of 3 kDa. This step removed unreacted sodium chloroacetate, glycolate, neutralizing salt, and low-molecular-weight reaction products, retaining the high-molecular-weight lignin sulfonate component containing carboxyl and sulfonic acid groups. The ultrafiltration temperature was controlled at 25–35 °C, the transmembrane pressure difference at 0.15–0.30 MPa, and the washing water volume was 4–6 times the initial volume of the retentate. When the washing water volume was less than 4 times, the residual amounts of small-molecular-weight reactants and inorganic salts increased; when it exceeded 6 times, the reduction in the proportion of low-molecular-weight components with continued washing decreased, and the concentration load increased.
[0066] The retentate obtained from washing and filtration is concentrated to a solid content of 18–22 wt%, and the pH is maintained at 7.8–8.3. When the solid content is below 18 wt%, the content of effective ingredients per unit volume is low, and the storage and dosing volume increases; when the solid content is above 22 wt%, the solution viscosity increases, and the dispersion rate after metering, transportation, and addition to the slurry decreases.
[0067] The carboxyl group increment of the obtained sodium carboxymethyl lignin, relative to the pre-fractionated sodium lignin sulfonate retainer, was controlled at 0.50–0.70 mmol / g dry basis, and the sulfonic acid group content was controlled at 1.40–1.80 mmol / g dry basis. The molar ratio of carboxyl group increment to sulfonic acid group content was controlled at 0.30–0.45:1. When the carboxyl group increment was below 0.50 mmol / g, the number of multi-site coordinations between lignin sulfonate segments and metal sites on the surfaces of sphalerite and pyrite decreased; when the carboxyl group increment was above 0.70 mmol / g, the binding capacity of the segments to metal sites increased, and the adsorption ratio on the galena surface increased accordingly. When the sulfonic acid group content was below 1.40 mmol / g, the hydration and extension of the segments decreased; when the sulfonic acid group content was above 1.80 mmol / g, the hydration degree and negative charge density of the segments increased, and the resistance of the segments to approach the mineral surface increased. When the molar ratio of carboxyl group increment to sulfonic acid group content is less than 0.30:1, the number of interfacial coordination sites is insufficient; when this molar ratio is greater than 0.45:1, the coordination effect of carboxyl groups is enhanced, and the proportion of non-selective adsorption on the galena surface increases.
[0068] The carboxyl group increment, sulfonic acid group content, and their molar ratio are structural parameters that must be satisfied simultaneously; arbitrary combinations of the endpoints of each parameter range are not allowed. In the aqueous size exclusion chromatogram of sodium carboxymethyl lignosulfonate, the percentage of the chromatographic peak area with a molecular weight less than 3000 Da is controlled to be no more than 5% of the total chromatographic peak area. When this percentage is higher than 5%, low molecular weight components are more easily dispersed in the slurry phase and react with metal ions in the solution, resulting in a decrease in the thickness and continuity of the adsorption layer formed on the mineral surface.
[0069] The principle of proportioning flotation reagent compositions
[0070] Based on a dry basis of sodium carboxymethyl lignosulfonate as 100 parts by weight, the remaining reagents, based on the mass of active ingredients, are: HQD82 1250–3340 parts, HQ77 125–385 parts, No. 2 oil 13–40 parts, and butyl xanthate 6–34 parts. The mass ratio of zinc sulfate to sodium sulfite in HQD82, based on the mass of active ingredients, is (1.0–2.0):1, preferably 3:2; the mass ratio of ethyl xanthate alkali metal salt to butyl xanthate alkali metal salt, based on the mass of active ingredients, in butyl xanthate is 1:(1.0–2.0), preferably 2:3. Preferably, HQD82 is 1660–2500 parts, HQ77 is 190–250 parts, No. 2 oil is 20–27 parts, and butyl xanthate is 11–17 parts.
[0071] The above weight ranges are determined based on the conversion of the amount of sodium carboxymethyl lignosulfonate and other reagents relative to the raw ore. The weight of HQD82 is the sum of the effective components of zinc sulfate and sodium sulfite, where the effective component of zinc sulfate is calculated as ZnSO4 and the effective component of sodium sulfite is calculated as Na2SO3. The weight of butyl xanthate is the sum of the effective components of ethyl xanthate alkali metal salt and butyl xanthate alkali metal salt. The specific weights of different reagents are selected corresponding to the actual amount of sodium carboxymethyl lignosulfonate added, ensuring that sodium carboxymethyl lignosulfonate, HQD82, HQ77, No. 2 oil, and butyl xanthate are within the specified unit raw ore addition range, and that the internal composition of HQD82 and butyl xanthate respectively meets the specified effective component mass ratio.
[0072] After HQD82 is added to a low-alkali slurry, the zinc hydrated or hydroxylated species formed by zinc sulfate and the sulfite ions formed by sodium sulfite jointly regulate the chemical state of the sphalerite and pyrite surfaces. The mass ratio of zinc sulfate to sodium sulfite, based on the effective component mass, is controlled at (1.0–2.0):1 to maintain the relative content of zinc components and sulfite ions in the slurry within the corresponding range. When this mass ratio is lower than 1.0:1, the proportion of zinc hydrated or hydroxylated species decreases, reducing the inorganic coverage of the sphalerite surface; when this mass ratio is higher than 2.0:1, the relative content of sulfite ions decreases, reducing its regulation of mineral surface oxidation sites and activated metal ions in the slurry. A mass ratio of 3:2 is preferred, allowing the inorganic surface species formed by zinc components and the interfacial regulation of sulfite ions to complement each other. Carboxymethyl lignin then forms multi-point coordination with zinc and iron sites on the sphalerite and pyrite surfaces through carboxyl groups, while sulfonic acid groups maintain the hydration layer around the polymer chain segments. HQD82 regulates the inorganic chemical state of the mineral surface, while carboxymethyl lignosulfonate forms a polymer adsorption hydration layer. The two respectively act on the inorganic species composition and interfacial hydration state of the mineral surface.
[0073] The dithiophosphate ions in HQ77 bind to lead sites on the galena surface via sulfur atoms, forming a lead-containing coordination adsorption layer that hydrophobizes the galena surface. HQ77 is added before sodium carboxymethyl lignin, ensuring that the lead sites on the galena surface are preferentially occupied by the collector. When sodium carboxymethyl lignin is added subsequently, it primarily contacts the surfaces of sphalerite and pyrite not covered by HQ77, reducing the proportion of active sites on the galena surface directly occupied by sodium carboxymethyl lignin.
[0074] The terpene alcohol molecules in Oil No. 2 are distributed at the gas-liquid interface, reducing the interfacial tension and regulating bubble size, foam water content, and foam stabilization time. Oil No. 2 is added after HQ77 and carboxymethyl lignosulfonate have completed their adsorption on the mineral surface, allowing the mineral surface conditioning process and the bubble formation process to proceed sequentially.
[0075] The ethyl xanthate is composed of ethyl xanthate alkali metal salt and butyl xanthate alkali metal salt, with a mass ratio of 1:(1.0-2.0) based on the effective component mass, preferably 2:3. Ethyl xanthate has a shorter hydrocarbon chain and higher water solubility; butyl xanthate has a longer hydrocarbon chain and a stronger hydrophobic effect on the surface of remaining sulfide minerals. When the mass ratio of ethyl xanthate alkali metal salt to butyl xanthate alkali metal salt is less than 1:2.0, the proportion of butyl xanthate increases, and its adsorption ratio on the surface of sphalerite and pyrite increases accordingly; when the mass ratio is greater than 1:1.0, the proportion of ethyl xanthate increases, and the recovery rate of remaining galena and lead-bearing intergrowth particles in the roughing tailings decreases. A mass ratio of 2:3 is used to ensure that the two xanthates are added together in the appropriate proportion during the scavenging stage. The ethyl xanthate is added during the scavenging stage and is not added to the roughing pulp simultaneously with HQ77.
[0076] Low-alkali flotation process principle
[0077] Lead-zinc-gold-silver sulfide ores are first ground to ensure that mineral particles smaller than 0.074 mm account for 70-80% of the total mineral particle mass. This fineness allows galena, sphalerite, pyrite, and gold- and silver-bearing intergrowths to form liberation interfaces that meet flotation requirements. Below 70%, insufficiently liberated lead-zinc intergrowths easily co-enter the froth product; above 80%, the proportion of fine particles and slime increases, leading to higher consumption of polymeric reagents and increased mechanical entrainment of hydrophilic minerals.
[0078] The solids concentration of the pulp is controlled between 35% and 42%. Below 35%, the collision frequency between mineral particles and reagents and bubbles decreases, reducing the throughput of the flotation equipment per unit volume. Above 42%, the apparent viscosity of the pulp and the intensity of interparticle collisions increase, affecting the diffusion and uniform adsorption of sodium carboxymethyl lignosulfonate in the pulp. The pulp temperature is controlled between 10 and 35°C. Below 10°C, the rates of polymer chain movement, reagent diffusion, and interfacial adsorption decrease. Above 35°C, the oxidation, hydrolysis, and desorption rates of some flotation reagents accelerate, and the froth layer state is also prone to change.
[0079] HQD82 was added to the grinding-processed slurry to adjust the pH to 7.8–8.8 and conditioning for 180 seconds. HQD82 first adjusts the inorganic chemical state of the sphalerite and pyrite surfaces, forming hydrophilic surface species before the subsequent addition of collectors. If the conditioning time is too short, the diffusion of zinc salt hydrolysis species and sulfite ions in the slurry and interfacial interactions are insufficient; as the conditioning time is further extended, the changes in the inorganic chemical state of the mineral surfaces tend to stabilize.
[0080] When the pulp pH is below 7.8, the formation of hydrated and hydroxylated species on the surfaces of sphalerite and pyrite is limited, and the interaction state between sulfite and oxidation sites on the mineral surface changes. When the pulp pH is above 8.8, the degree of oxidation and hydroxylation on the galena surface increases, affecting the binding of HQ77 to lead sites on the galena surface. Controlling the pulp pH between 7.8 and 8.8 allows HQD82, HQ77, and carboxymethyl lignosulfonate to act sequentially on the corresponding mineral interfaces while maintaining low-alkali flotation conditions.
[0081] After preparing the HQD82 slurry, add HQ77 and stir for 120–180 s. The dithiophosphate ions in HQ77 preferentially bind to lead sites on the galena surface, forming a collector adsorption layer. When stirring for less than 120 s, the dispersion of HQ77 in the slurry and its adsorption on the galena surface are insufficient; after stirring for more than 180 s, the adsorption on the galena surface tends to stabilize, and continued stirring will increase the contact time between HQ77 and non-target sulfide minerals.
[0082] After HQ77 adsorption is complete, 70-80% of the total sodium carboxymethyl lignosulfonate is added and stirred for 60-120 seconds. HQ77 pre-occupies some lead sites on the galena surface. The subsequently added sodium carboxymethyl lignosulfonate mainly contacts areas on the sphalerite and pyrite surfaces that remain hydrophilic or have metallic sites, forming a polymer adsorption layer through carboxyl coordination and sulfonic acid hydration. When the first portion of sodium carboxymethyl lignosulfonate is less than 70% of the total, the surface coverage of sphalerite and pyrite before roughing is insufficient; when it exceeds 80% of the total, the amount of reagent reserved for supplementary coverage in the cleaning stage is reduced. When the stirring time is less than 60 seconds, the diffusion and surface adsorption of sodium carboxymethyl lignosulfonate in the slurry are insufficient; after the stirring time exceeds 120 seconds, the increase in interfacial coverage tends to stabilize, and the slurry conditioning cycle before roughing is prolonged.
[0083] After adding the first portion of carboxymethyl lignosulfonate, add oil No. 2 and stir for 30–60 seconds, followed by roughing with aeration for 4 minutes. Adding oil No. 2 after the initial stirring time allows the collection and inhibition processes on the mineral surface to complete before the bubble formation process. When the stirring time is less than 30 seconds, oil No. 2 is unevenly dispersed in the slurry; when the stirring time exceeds 60 seconds, its further impact on the gas-liquid interface is limited. When the roughing time is less than 4 minutes, the collision, adhesion, and flotation processes of hydrophobic galena with bubbles are insufficient; further extending the roughing time increases the proportion of inhibited sphalerite, pyrite, and hydrophilic gangue that are mechanically carried into the roughing concentrate.
[0084] Add the remaining 20-30% of carboxymethyl lignosulfonate to the roughing concentrate, stir for 90-150 s, and then perform a 3-minute cleaning process. During the roughing process, particle collision, surface abrasion, and pulp dilution will cause some sphalerite and pyrite surfaces to be re-exposed. The subsequently added carboxymethyl lignosulfonate replenishes and covers the re-exposed zinc and iron sites. If the second portion of carboxymethyl lignosulfonate is less than 20% of the total, the replenishment coverage is insufficient; if it exceeds 30% of the total, the concentration of polymeric reagents added to the cleaning pulp increases, and the probability of it contacting galena and undergoing non-selective adsorption increases. If the stirring time is less than 90 s, the replenishment adsorption is insufficient; after more than 150 s, the interfacial coverage tends to stabilize. The cleaning time is controlled at 3 minutes to allow galena in the roughing concentrate to continue to accumulate, while limiting the entry of sphalerite, pyrite, and hydrophilic gangue into the cleaned froth product.
[0085] Eu-ethyl xanthate was added to the roughing tailings and stirred for 60 seconds, followed by scavenging for 8 minutes. Eu-ethyl xanthate binds to the surfaces of galena, lead-bearing intergrowth particles, and some gold and silver carrier particles in the roughing tailings that were not fully covered by HQ77. Limiting the eu-ethyl xanthate to the scavenging stage avoids increasing the collection of sphalerite and pyrite during the roughing stage. The scavenging time is controlled at 8 minutes to provide time for the remaining hydrophobic particles with lower concentrations in the tailings to collide with air bubbles and float to the surface.
[0086] The total addition amount of sodium carboxymethyl lignin, on a dry basis, is 30–60 g / t of raw ore. When the addition amount is less than 30 g / t of raw ore, the polymer adsorption layer on the surface of sphalerite and pyrite is insufficient; when the addition amount is greater than 60 g / t of raw ore, the concentration of unadsorbed polymers in the slurry increases, and the probability of non-selective adsorption of sodium carboxymethyl lignin on the surface of galena increases. The addition amounts of HQD82, HQ77, No. 2 oil, and butyl xanthate, based on the effective ingredient, are 750–1000 g / t of raw ore, 75–115 g / t of raw ore, 8–12 g / t of raw ore, and 4–10 g / t of raw ore, respectively. The unit raw ore addition amount of each reagent corresponds to the composition ratio based on 100 parts by weight of sodium carboxymethyl lignin on a dry basis.
[0087] When the addition amount of HQD82 is less than 750 g / t of raw ore, the formation of inorganic hydrophilic species on the surface of sphalerite and pyrite is insufficient; when the addition amount is greater than 1000 g / t of raw ore, the concentration of inorganic ions in the slurry and the consumption of reagents increase, and the chain extension state of subsequent polymer reagents is altered. When the addition amount of HQ77 is less than 75 g / t of raw ore, the collector coverage on the surface of galena is insufficient; when the addition amount is greater than 115 g / t of raw ore, the concentration of residual collector in the liquid phase of the slurry increases, and its adsorption probability on the surface of sphalerite, pyrite and other sulfide minerals is increased.
[0088] When the addition of No. 2 oil is less than 8 g / t of raw ore, the formation and duration of the foam layer are insufficient; when the addition is greater than 12 g / t of raw ore, the proportion of fine bubbles and stable foam increases, and the mechanical entrainment of hydrophilic gangue and suppressed minerals increases. When the addition of ethyl butyl xanthate is less than 4 g / t of raw ore, the recovery of residual galena and lead-bearing intergrowth particles in the roughing tailings is insufficient; when the addition is greater than 10 g / t of raw ore, the proportion of sphalerite and pyrite entering the scavenging foam product increases.
[0089] Both the tailings and scavenging concentrate contain intermediate mineral particles that are not fully liberated or have varying degrees of surface reagent coverage. The tailings and scavenging concentrate are returned to the roughing process, where the lead minerals are re-entered into the HQD82 pulp conditioning, HQ77 collector, carboxymethyl lignosulfonate interface covering, and bubble mineralization processes. This intermediate product return constitutes a low-alkali closed-circuit flotation process that seamlessly integrates roughing, cleaning, and scavenging.
[0090] Example 1
[0091] This embodiment provides a flotation reagent composition under low-alkali conditions and its application.
[0092] (1) Preparation of sodium carboxymethyl lignosulfonate
[0093] Based on 100 parts by weight of the sodium lignosulfonate residue obtained in step P2 (dry basis), the raw materials for preparing carboxymethyl lignosulfonate include 100 parts by weight of the sodium lignosulfonate residue, 38 parts by weight of sodium chloroacetate, 14.75 parts by weight of sodium hydroxide, and 650 parts by weight of water for reaction preparation. The molar ratio of total sodium hydroxide to total sodium chloroacetate is 1.13:1. The pH of the reaction solution is adjusted using 10% hydrochloric acid. The washing and filtering water used in steps P2 and P6 is calculated separately. The water used for reaction preparation is allocated in steps P1 and P3-P5 according to the solid content and the preparation requirements of the aqueous solutions of each material.
[0094] P1. Add sufficient sodium lignosulfonate to water to prepare an aqueous solution of sodium lignosulfonate with a solid content of 15 wt%. Stir at 30°C for 45 min and filter to remove insoluble matter.
[0095] P2, the sodium lignosulfonate aqueous solution obtained in step P1 is filtered through an ultrafiltration membrane with a nominal molecular weight cutoff of 5 kDa. The ultrafiltration temperature is 30°C, the transmembrane pressure difference is 0.225 MPa, and the volume of washing water is 3.5 times the initial volume of the retentate. The retentate is collected and concentrated to a solid content of 17.5 wt%. 100 parts by weight of the retentate (dry basis) is used as the material for subsequent reactions.
[0096] P3. Add 10.33 parts by weight of sodium hydroxide to the retentate obtained in step P2, adjust the pH of the material to 12.0 at 32°C, and alkalize for 30 min.
[0097] P4. Prepare an aqueous solution of 70% (26.6 parts by weight) of sodium chloroacetate and add it dropwise to the material obtained in step P3 over 75 minutes. During the dropwise addition, maintain the reaction temperature at 38°C and the pH at 11.8. After the dropwise addition is complete, continue the reaction for 40 minutes.
[0098] P5. The material obtained in step P4 is heated to 48°C at a rate of 0.35°C / min. The remaining 11.4 parts by weight of sodium chloroacetate and the second part of sodium hydroxide (4.42 parts by weight) are prepared into aqueous solutions, and added dropwise simultaneously over 45 min. The pH is maintained at 11.3 during the dropwise addition. After the dropwise addition is completed, the reaction continues at 48°C for 2.5 h.
[0099] P6. Cool the reaction solution obtained in step P5 to 28°C, and add 10% hydrochloric acid to adjust the pH to 8.0. Wash the neutralized reaction solution through an ultrafiltration membrane with a nominal molecular weight cutoff of 3 kDa. The ultrafiltration temperature is 30°C, the transmembrane pressure difference is 0.225 MPa, and the volume of washing water is 5 times the initial volume of the retentate. Collect the retentate.
[0100] P7. Concentrate the retentate obtained in step P6 to a solid content of 20 wt%, and adjust the pH to 8.0 to obtain sodium carboxymethyl lignin. The carboxyl lignin sodium obtained has a carboxyl group increment of 0.60 mmol / g dry basis and a sulfonic acid group content of 1.60 mmol / g dry basis compared to the sodium lignin sulfonate retentate obtained in step P2. The molar ratio of carboxyl group increment to sulfonic acid group content is 0.375:1. In its aqueous phase size exclusion chromatogram, the percentage of the chromatographic peak area with a molecular weight less than 3000 Da is no more than 3% of the total chromatographic peak area.
[0101] (2) Flotation reagent compositions and their applications
[0102] Based on 100 parts by weight of sodium carboxymethyl lignosulfonate (dry basis), and calculated according to the mass of the active ingredients, the flotation reagent composition of this embodiment includes 100 parts by weight of sodium carboxymethyl lignosulfonate, 1944.44 parts by weight of HQD82, 233.33 parts by weight of HQ77, 22.22 parts by weight of No. 2 oil, and 11.11 parts by weight of butyl xanthate. HQD82 is composed of 1166.67 parts by weight of zinc sulfate and 777.77 parts by weight of sodium sulfite, with an active ingredient mass ratio of 3:2. The butyl xanthate is composed of 4.44 parts by weight of sodium ethyl xanthate and 6.67 parts by weight of sodium butyl xanthate, with an active ingredient mass ratio of 2:3. The active ingredient mass of zinc sulfate is calculated as ZnSO4, and the active ingredient mass of sodium sulfite is calculated as Na2SO3. Sodium carboxymethyl lignosulfonate, HQD82, HQ77, No. 2 oil, and butyl xanthate are formulated and packaged independently.
[0103] During the flotation process, 45 g of sodium carboxymethyl lignosulfonate, 875 g of HQD82, 105 g of HQ77, 10 g of No. 2 oil, and 5 g of butyl xanthate were added per ton of raw ore. The 875 g of HQD82 consisted of 525 g of zinc sulfate and 350 g of sodium sulfite; the 5 g of butyl xanthate consisted of 2 g of sodium ethyl xanthate and 3 g of sodium butyl xanthate. The amount of sodium carboxymethyl lignosulfonate added was on a dry basis, and the amounts of zinc sulfate, sodium sulfite, HQ77, No. 2 oil, sodium ethyl xanthate, and sodium butyl xanthate were all based on their effective components.
[0104] M1 involves grinding lead-zinc-gold-silver sulfide ores until mineral particles with a diameter of less than 0.074 mm account for 75% of the total mass of mineral particles. Water is then added to prepare a slurry with a solid mass concentration of 38%, and the slurry temperature is controlled at 25℃.
[0105] M2, add 875 g / t of HQD82 of raw ore to the slurry obtained in step M1. The HQD82 is composed of 525 g / t of zinc sulfate and 350 g / t of sodium sulfite of raw ore. Adjust the pH of the slurry to 8.3 and adjust the slurry for 3 min.
[0106] M3. Add 105 g / t of raw ore HQ77 to the slurry obtained in step M2 and stir for 150 s.
[0107] M4. Add 75% of the total amount of sodium carboxymethyl lignosulfonate, i.e., 33.75 g / t of sodium carboxymethyl lignosulfonate from the raw ore, to the slurry obtained in step M3, and stir for 90 s.
[0108] M5. Add 10 g / t of No. 2 oil to the slurry obtained in step M4, stir for 45 s, and then aerate for roughing for 4 min to obtain roughing concentrate and roughing tailings.
[0109] M6. Add the remaining 25% of sodium carboxymethyl lignosulfonate, i.e., 11.25 g / t of sodium carboxymethyl lignosulfonate in the rough concentrate obtained in step M5, stir for 120 s and then finely concentrate for 3 min to obtain lead concentrate and finely concentrated tailings. Return the finely concentrated tailings to the roughing operation.
[0110] M7. Add 5 g / t of sodium ethyl xanthate from the raw ore to the roughing tailings obtained in step M5. The sodium ethyl xanthate consists of 2 g / t of sodium ethyl xanthate and 3 g / t of sodium butyl xanthate from the raw ore. Stir for 60 s and then scaveng for 8 min to obtain scavenged concentrate and flotation tailings. Return the scavenged concentrate to the roughing operation.
[0111] Example 2
[0112] This embodiment provides a flotation reagent composition under low-alkali conditions and its application.
[0113] (1) Preparation of sodium carboxymethyl lignosulfonate
[0114] Based on 100 parts by weight of the sodium lignosulfonate residue obtained in step P2 (dry basis), the raw materials for preparing carboxymethyl lignosulfonate include 100 parts by weight of the sodium lignosulfonate residue, 32 parts by weight of sodium chloroacetate, 11.87 parts by weight of sodium hydroxide, and 550 parts by weight of water for reaction preparation. The molar ratio of total sodium hydroxide to total sodium chloroacetate is 1.08:1. The pH of the reaction solution is adjusted using 10% hydrochloric acid. The washing and filtering water used in steps P2 and P6 is calculated separately. The water used for reaction preparation is allocated in steps P1 and P3-P5 according to the solid content and the preparation requirements of the aqueous solutions of each material.
[0115] P1. Add sufficient sodium lignosulfonate to water to prepare an aqueous solution of sodium lignosulfonate with a solid content of 12 wt%. Stir at 25°C for 30 min and filter to remove insoluble matter.
[0116] P2, the sodium lignosulfonate aqueous solution obtained in step P1 is washed through an ultrafiltration membrane with a nominal molecular weight cutoff of 5 kDa. The ultrafiltration temperature is 25°C, the transmembrane pressure difference is 0.15 MPa, and the volume of washing water is three times the initial volume of the retentate. The retentate is collected and concentrated to a solid content of 15 wt%. 100 parts by weight of the retentate (dry basis) is used as the material for subsequent reactions.
[0117] P3. Add 7.72 parts by weight of sodium hydroxide to the retentate obtained in step P2, adjust the pH of the material to 11.8 at 30°C, and alkalize for 20 min.
[0118] P4. Prepare an aqueous solution of 65% (20.8 parts by weight) of sodium chloroacetate and add it dropwise to the material obtained in step P3 over 60 minutes. During the dropwise addition, maintain the reaction temperature at 36°C and the pH at 11.6. After the dropwise addition is complete, continue the reaction for another 30 minutes.
[0119] P5. The material obtained in step P4 is heated to 46°C at a rate of 0.2°C / min. The remaining 11.2 parts by weight of sodium chloroacetate and the second part of sodium hydroxide (4.15 parts by weight) are separately prepared into aqueous solutions, and added dropwise simultaneously over 30 min. The pH is maintained at 11.1 during the dropwise addition. After the dropwise addition is completed, the reaction continues at 46°C for 2 h.
[0120] P6. Cool the reaction solution obtained in step P5 to 30°C, and add 10% hydrochloric acid to adjust the pH to 7.8. Wash the neutralized reaction solution through an ultrafiltration membrane with a nominal molecular weight cutoff of 3 kDa. The ultrafiltration temperature is 25°C, the transmembrane pressure difference is 0.15 MPa, and the volume of washing water is four times the initial volume of the retentate. Collect the retentate.
[0121] P7. The retentate obtained in step P6 is concentrated to a solid content of 18 wt%, and the pH is adjusted to 7.8 to obtain sodium carboxymethyl lignin. The carboxyl group increment of the obtained sodium carboxymethyl lignin compared to the sodium lignin sulfonate retentate obtained in step P2 is 0.50 mmol / g dry basis, and the sulfonic acid group content is 1.67 mmol / g dry basis. The molar ratio of carboxyl group increment to sulfonic acid group content is 0.30:1. In its aqueous phase size exclusion chromatogram, the percentage of peak area with a molecular weight less than 3000 Da is no more than 5% of the total peak area.
[0122] (2) Flotation reagent compositions and their applications
[0123] Based on 100 parts by weight of sodium carboxymethyl lignosulfonate (dry basis), and calculated according to the mass of the active ingredients, the flotation reagent composition of this embodiment includes 100 parts by weight of sodium carboxymethyl lignosulfonate, 2500 parts by weight of HQD82, 250 parts by weight of HQ77, 26.67 parts by weight of No. 2 oil, and 13.33 parts by weight of butyl xanthate. HQD82 is composed of 1500 parts by weight of zinc sulfate and 1000 parts by weight of sodium sulfite, with an active ingredient mass ratio of zinc sulfate to sodium sulfite of 3:2. The butyl xanthate is composed of 5.33 parts by weight of sodium ethyl xanthate and 8.00 parts by weight of sodium ethyl xanthate, with an active ingredient mass ratio of sodium ethyl xanthate to sodium butyl xanthate of 2:3. The active ingredient mass of zinc sulfate is calculated as ZnSO4, and the active ingredient mass of sodium sulfite is calculated as Na2SO3. Sodium carboxymethyl lignosulfonate, HQD82, HQ77, No. 2 oil, and butyl xanthate are prepared and packaged independently.
[0124] During the flotation process, 30 g of sodium carboxymethyl lignosulfonate, 750 g of HQD82, 775 g of HQ777, 8 g of No. 2 oil, and 4 g of butyl xanthate were added per ton of raw ore. The 750 g of HQD82 consisted of 450 g of zinc sulfate and 300 g of sodium sulfite; the 4 g of butyl xanthate consisted of 1.6 g of sodium ethyl xanthate and 2.4 g of sodium butyl xanthate. The amount of sodium carboxymethyl lignosulfonate added was on a dry basis, and the amounts of zinc sulfate, sodium sulfite, HQ777, No. 2 oil, sodium ethyl xanthate, and sodium butyl xanthate were all based on their effective components.
[0125] M1 involves grinding lead-zinc-gold-silver sulfide ores until mineral particles with a diameter of less than 0.074 mm account for 70% of the total mass of mineral particles. Water is then added to prepare a slurry with a solid mass concentration of 35%, and the slurry temperature is controlled at 10℃.
[0126] M2, add 750 g / t HQD82 of raw ore to the slurry obtained in step M1. The HQD82 is composed of 450 g / t zinc sulfate of raw ore and 300 g / t sodium sulfite of raw ore. Adjust the pH of the slurry to 7.8 and adjust the slurry for 3 min.
[0127] M3. Add 75 g / t of raw ore HQ77 to the slurry obtained in step M2 and stir for 120 s.
[0128] M4. Add 70% of the total amount of sodium carboxymethyl lignosulfonate, i.e., 21 g / t of sodium carboxymethyl lignosulfonate from the raw ore, to the slurry obtained in step M3, and stir for 60 s.
[0129] M5. Add 8 g / t of No. 2 oil to the slurry obtained in step M4, stir for 30 s, and then aerate for 4 min to obtain rough concentrate and rough tailings.
[0130] M6. Add the remaining 30% of sodium carboxymethyl lignosulfonate, i.e., 9 g / t of sodium carboxymethyl lignosulfonate in the rough concentrate obtained in step M5, stir for 90 s and then finely concentrate for 3 min to obtain lead concentrate and finely concentrated tailings. Return the finely concentrated tailings to the rough concentrate operation.
[0131] M7. Add 4 g / t of sodium ethyl xanthate from the raw ore to the roughing tailings obtained in step M5. The sodium ethyl xanthate consists of 1.6 g / t of sodium ethyl xanthate and 2.4 g / t of sodium butyl xanthate from the raw ore. Stir for 60 s and then scaveng for 8 min to obtain scavenged concentrate and flotation tailings. Return the scavenged concentrate to the roughing operation.
[0132] Example 3
[0133] This embodiment provides a flotation reagent composition under low-alkali conditions and its application.
[0134] (1) Preparation of sodium carboxymethyl lignosulfonate
[0135] Based on 100 parts by weight of the sodium lignosulfonate residue obtained in step P2 (dry basis), the raw materials for preparing carboxymethyl lignosulfonate include 100 parts by weight of the sodium lignosulfonate residue, 44 parts by weight of sodium chloroacetate, 17.83 parts by weight of sodium hydroxide, and 750 parts by weight of water for reaction preparation. The molar ratio of total sodium hydroxide to total sodium chloroacetate is 1.18:1. The pH of the reaction solution is adjusted using 10% hydrochloric acid. The washing and filtering water used in steps P2 and P6 is calculated separately. The water used for reaction preparation is allocated in steps P1 and P3-P5 according to the solid content and the preparation requirements of the aqueous solutions of each material.
[0136] P1. Add sufficient sodium lignosulfonate to water to prepare an aqueous solution of sodium lignosulfonate with a solid content of 18 wt%. Stir at 35°C for 60 min and filter to remove insoluble matter.
[0137] P2, the sodium lignosulfonate aqueous solution obtained in step P1 is washed through an ultrafiltration membrane with a nominal molecular weight cutoff of 5 kDa. The ultrafiltration temperature is 35°C, the transmembrane pressure difference is 0.30 MPa, and the volume of washing water is 4 times the initial volume of the retentate. The retentate is collected and concentrated to a solid content of 20 wt%. 100 parts by weight of the retentate (dry basis) is used as the material for subsequent reactions.
[0138] P3. Add 13.37 parts by weight of sodium hydroxide to the retentate obtained in step P2, adjust the pH of the material to 12.2 at 34°C, and alkalize for 40 min.
[0139] P4. Prepare an aqueous solution of 75% (33 parts by weight) of sodium chloroacetate and add it dropwise to the material obtained in step P3 over 90 minutes. During the dropwise addition, maintain the reaction temperature at 40°C and the pH at 12.0. After the dropwise addition is complete, continue the reaction for 45 minutes.
[0140] P5. The material obtained in step P4 is heated to 50°C at a rate of 0.5°C / min. The remaining 11 parts by weight of sodium chloroacetate and the second part of sodium hydroxide (4.46 parts by weight) are prepared into aqueous solutions, and added dropwise simultaneously over 60 min. The pH is maintained at 11.5 during the dropwise addition. After the dropwise addition is completed, the reaction is continued at 50°C for 3 h.
[0141] P6. Cool the reaction solution obtained in step P5 to 30°C, and add 10% hydrochloric acid to adjust the pH to 8.3. Wash the neutralized reaction solution through an ultrafiltration membrane with a nominal molecular weight cutoff of 3 kDa. The ultrafiltration temperature is 35°C, the transmembrane pressure difference is 0.30 MPa, and the volume of washing water is 6 times the initial volume of the retentate. Collect the retentate.
[0142] P7. The retentate obtained in step P6 is concentrated to a solid content of 22 wt%, and the pH is adjusted to 8.3 to obtain sodium carboxymethyl lignin. The carboxyl group increment of the obtained sodium carboxymethyl lignin compared with the sodium lignin sulfonate retentate obtained in step P2 is 0.70 mmol / g dry basis, and the sulfonic acid group content is 1.56 mmol / g dry basis. The molar ratio of carboxyl group increment to sulfonic acid group content is 0.45:1. In its aqueous phase size exclusion chromatogram, the percentage of the chromatographic peak area with a molecular weight less than 3000 Da is no more than 5% of the total chromatographic peak area.
[0143] (2) Flotation reagent compositions and their applications
[0144] Based on 100 parts by weight of sodium carboxymethyl lignosulfonate (dry basis), and calculated according to the mass of the active ingredients, the flotation reagent composition of this embodiment includes 100 parts by weight of sodium carboxymethyl lignosulfonate, 1666.67 parts by weight of HQD82, 191.67 parts by weight of HQ77, 20 parts by weight of No. 2 oil, and 16.67 parts by weight of butyl xanthate. HQD82 consists of 1000 parts by weight of zinc sulfate and 666.67 parts by weight of sodium sulfite, with an active ingredient mass ratio of zinc sulfate to sodium sulfite of 3:2. The butyl xanthate consists of 6.67 parts by weight of sodium ethyl xanthate and 10.00 parts by weight of sodium butyl xanthate, with an active ingredient mass ratio of sodium ethyl xanthate to sodium butyl xanthate of 2:3. The active ingredient mass of zinc sulfate is calculated as ZnSO4, and the active ingredient mass of sodium sulfite is calculated as Na2SO3. Sodium carboxymethyl lignosulfonate, HQD82, HQ77, No. 2 oil, and butyl xanthate are formulated and packaged independently.
[0145] During the flotation process, 60 g of sodium carboxymethyl lignosulfonate, 1000 g of HQD82, 115 g of HQ77, 12 g of No. 2 oil, and 10 g of butyl xanthate were added per ton of raw ore. Specifically, 1000 g of HQD82 consisted of 600 g of zinc sulfate and 400 g of sodium sulfite; 10 g of butyl xanthate consisted of 4 g of sodium ethyl xanthate and 6 g of sodium butyl xanthate. The amount of sodium carboxymethyl lignosulfonate added was on a dry basis, and the amounts of zinc sulfate, sodium sulfite, HQ77, No. 2 oil, sodium ethyl xanthate, and sodium butyl xanthate were all based on their effective components.
[0146] M1 involves grinding lead-zinc-gold-silver sulfide ores until mineral particles with a diameter of less than 0.074 mm account for 80% of the total mass of mineral particles. Water is then added to prepare a slurry with a solid mass concentration of 42%, and the slurry temperature is controlled at 35℃.
[0147] M2, add 1000 g / t HQD82 of raw ore to the slurry obtained in step M1. The HQD82 is composed of 600 g / t zinc sulfate of raw ore and 400 g / t sodium sulfite of raw ore. Adjust the pH of the slurry to 8.8 and adjust the slurry for 3 min.
[0148] M3. Add 115 g / t of raw ore HQ77 to the slurry obtained in step M2 and stir for 180 s.
[0149] M4. Add 80% of the total amount of sodium carboxymethyl lignosulfonate, i.e., 48 g / t of sodium carboxymethyl lignosulfonate from the raw ore, to the slurry obtained in step M3, and stir for 120 s.
[0150] M5. Add 12 g / t of No. 2 oil to the slurry obtained in step M4, stir for 60 s, and then aerate for 4 min to obtain rough concentrate and rough tailings.
[0151] M6. Add the remaining 20% of sodium carboxymethyl lignosulfonate (i.e., 12 g / t of sodium carboxymethyl lignosulfonate from the raw ore) to the rough concentrate obtained in step M5. Stir for 150 s and then finely concentrate for 3 min to obtain lead concentrate and finely concentrated tailings. Return the finely concentrated tailings to the roughing operation.
[0152] M7. Add 10 g / t of sodium ethyl xanthate from the raw ore to the roughing tailings obtained in step M5. The sodium ethyl xanthate consists of 4 g / t of sodium ethyl xanthate and 6 g / t of sodium butyl xanthate from the raw ore. Stir for 60 s and then scaveng for 8 min to obtain scavenging concentrate and flotation tailings. Return the scavenging concentrate to the roughing operation.
[0153] Comparative Example 1
[0154] This comparative example provides a flotation reagent composition under low-alkali conditions and its application.
[0155] (1) Preparation of sodium carboxymethyl lignosulfonate
[0156] This comparative example does not prepare or add carboxymethyl lignosulfonate.
[0157] (2) Flotation reagent compositions and their applications
[0158] Based on each ton of raw ore, prepare 1000 g of lime, 1000 g of zinc sulfate, 90 g of No. 25 black powder, 10 g of No. 2 oil, and 5 g of butyl xanthate. The butyl xanthate consists of 2 g of sodium ethyl xanthate and 3 g of sodium butyl xanthate, with an effective component mass ratio of 2:3. The amounts of each reagent added are based on their effective components.
[0159] Step M1 is exactly the same as in Example 1.
[0160] M2: Add 1000 g / t lime (based on raw ore) to the slurry obtained in step M1, adjust the slurry for 3 minutes, then add 1000 g / t zinc sulfate (based on raw ore), and adjust the slurry for 2 minutes. The pH of the slurry is determined by the amount of lime added.
[0161] M3. Add 90 g / t of raw ore No. 25 black powder to the slurry obtained in step M2 and stir for 180 s.
[0162] M4. Add 10 g / t of No. 2 oil to the slurry obtained in step M3, stir for 45 s, and then aerate for roughing for 4 min to obtain roughing concentrate and roughing tailings.
[0163] M5, refine the rough concentrate obtained in step M4 for 3 minutes to obtain lead concentrate and refined tailings, and return the refined tailings to the roughing operation.
[0164] M6. Add 5 g / t of sodium ethyl xanthate from the raw ore to the roughing tailings obtained in step M4. The sodium ethyl xanthate consists of 2 g / t of sodium ethyl xanthate and 3 g / t of sodium butyl xanthate from the raw ore. Stir for 60 s and then scaveng for 8 min to obtain scavenging concentrate and flotation tailings. Return the scavenging concentrate to the roughing operation.
[0165] Comparative Example 2
[0166] This comparative example provides a flotation reagent composition under low-alkali conditions and its application.
[0167] (1) Preparation of sodium carboxymethyl lignosulfonate
[0168] This comparative example does not prepare or add carboxymethyl lignosulfonate.
[0169] (2) Flotation reagent compositions and their applications
[0170] Based on each ton of raw ore, prepare 875 g of HQD82, 105 g of HQ77, 10 g of No. 2 oil, and 5 g of butyl xanthate. HQD82 consists of 525 g of zinc sulfate and 350 g of sodium sulfite, with a zinc sulfate to sodium sulfite effective component mass ratio of 3:2. The butyl xanthate consists of 2 g of sodium ethyl xanthate and 3 g of sodium butyl xanthate, with an ethyl xanthate to sodium butyl xanthate effective component mass ratio of 2:3. The effective component mass of zinc sulfate is calculated as ZnSO4, and the effective component mass of sodium sulfite is calculated as Na2SO3. The amounts of the remaining reagents are calculated based on their respective effective components.
[0171] Step M1 is exactly the same as in Example 1.
[0172] Step M2 is exactly the same as in Example 1.
[0173] The M3 step is exactly the same as in Example 1.
[0174] M4: After step M3 is completed, carboxymethyl lignosulfonate is not added; subsequent processing proceeds directly.
[0175] M5. Add 10 g / t of No. 2 oil to the slurry obtained in step M4, stir for 45 s, and then aerate for roughing for 4 min to obtain roughing concentrate and roughing tailings.
[0176] M6. The rough concentrate obtained in step M5 is further refined for 3 minutes to obtain lead concentrate and refined tailings. The refined tailings are then returned to the roughing operation.
[0177] The steps in M7 are exactly the same as in Example 1.
[0178] Comparative Example 3
[0179] This comparative example provides a flotation reagent composition under low-alkali conditions and its application.
[0180] (1) Preparation of conventional carboxymethylated sodium lignosulfonate
[0181] Based on 100 parts by weight of sodium lignosulfonate (dry basis), the raw materials for the preparation of conventional carboxymethylated sodium lignosulfonate include 100 parts by weight of sodium lignosulfonate, 38 parts by weight of sodium chloroacetate, 14.75 parts by weight of sodium hydroxide, and 650 parts by weight of water for reaction preparation. The molar ratio of sodium hydroxide to sodium chloroacetate is 1.13:1. The pH of the reaction solution is adjusted using 10% hydrochloric acid. The water used for reaction preparation is allocated according to the solid content of the solution and the preparation requirements of the aqueous solutions of each material.
[0182] P1. Sodium lignosulfonate was added to water to prepare an aqueous solution of sodium lignosulfonate with a solid content of 15 wt%. The solution was stirred at 30°C for 45 min and then filtered to remove insoluble matter.
[0183] P2, The sodium lignosulfonate aqueous solution obtained in step P1 is not subjected to 5 kDa ultrafiltration pre-fractionation.
[0184] P3. Add 14.75 parts by weight of sodium hydroxide to the sodium lignosulfonate aqueous solution obtained in step P1, adjust the pH of the material to 11.3, and alkalize at 32°C for 30 min.
[0185] P4. Prepare an aqueous solution of 38 parts by weight of sodium chloroacetate. Heat the material obtained in step P3 to 48°C and continuously add all the sodium chloroacetate dropwise over 60 minutes. Maintain the pH at 11.3 during the dropwise addition. Continue the reaction for 3 hours after the dropwise addition is complete.
[0186] P5, this comparative example does not involve the stepwise addition of sodium chloroacetate and sodium hydroxide in the second stage.
[0187] P6. Cool the reaction solution obtained in step P4 to 28°C, add 10% hydrochloric acid to adjust the pH to 8.0, and do not perform 3 kDa ultrafiltration washing.
[0188] P7. Concentrate the reaction solution obtained in step P6 to a solid content of 20 wt%, and adjust the pH to 8.0 to obtain conventional carboxymethylated sodium lignin sulfonate.
[0189] (2) Flotation reagent compositions and their applications
[0190] Based on 100 parts by weight of conventional carboxymethylated lignin sulfonate (dry basis), and converted according to the mass of the active ingredients, the flotation reagent composition in this comparative example includes 100 parts by weight of conventional carboxymethylated lignin sulfonate, 1944.44 parts by weight of HQD82, 233.33 parts by weight of HQ77, 22.22 parts by weight of No. 2 oil, and 11.11 parts by weight of butyl xanthate. Each reagent is prepared and packaged independently.
[0191] During the flotation process, based on one ton of raw ore, the following reagents were prepared: 45 g of conventional carboxymethylated lignin sulfonate, 875 g of HQD82, 105 g of HQ77, 10 g of No. 2 oil, and 5 g of butyl xanthate. HQD82 consisted of 525 g of zinc sulfate and 350 g of sodium sulfite, with a zinc sulfate to sodium sulfite effective component mass ratio of 3:2. The butyl xanthate consisted of 2 g of ethyl xanthate and 3 g of butyl xanthate, with an ethyl xanthate to butyl xanthate effective component mass ratio of 2:3. The amounts of conventional carboxymethylated lignin sulfonate added were on a dry basis, the effective component mass of zinc sulfate was calculated as ZnSO4, the effective component mass of sodium sulfite was calculated as Na2SO3, and the amounts of the other reagents were calculated based on their respective effective components.
[0192] Step M1 is exactly the same as in Example 1.
[0193] Step M2 is exactly the same as in Example 1.
[0194] The M3 step is exactly the same as in Example 1.
[0195] M4. Add 75% of the total amount of conventional carboxymethylated lignin sulfonate, i.e., 33.75 g / t of conventional carboxymethylated lignin sulfonate, to the slurry obtained in step M3, and stir for 90 s.
[0196] The steps in M5 are exactly the same as in Example 1.
[0197] M6. Add the remaining 25% of conventional carboxymethylated lignin sulfonate (i.e., 11.25 g / t of conventional carboxymethylated lignin sulfonate) to the rough concentrate obtained in step M5. Stir for 120 s and then finely concentrate for 3 min to obtain lead concentrate and finely concentrated tailings. Return the finely concentrated tailings to the roughing operation.
[0198] The steps in M7 are exactly the same as in Example 1.
[0199] Comparative Example 4
[0200] This comparative example provides a flotation reagent composition under low-alkali conditions and its application.
[0201] (1) Preparation of sodium carboxymethyl lignosulfonate
[0202] The raw materials and steps P1 to P7 for the preparation of sodium carboxymethyl lignosulfonate are exactly the same as in Example 1.
[0203] (2) Flotation reagent compositions and their applications
[0204] Based on 100 parts by weight of sodium carboxymethyl lignosulfonate (dry basis), and converted according to the mass of the active ingredients, the flotation reagent composition of this comparative example includes 100 parts by weight of sodium carboxymethyl lignosulfonate, 1944.44 parts by weight of HQD82, 233.33 parts by weight of HQ77, 22.22 parts by weight of No. 2 oil, and 11.11 parts by weight of butyl xanthate. Each reagent is prepared and packaged independently.
[0205] During the flotation process, based on each ton of raw ore, the following reagents were prepared: 45 g of sodium carboxymethyl lignosulfonate, 875 g of HQD82, 105 g of HQ77, 10 g of No. 2 oil, and 5 g of butyl xanthate. HQD82 consisted of 525 g of zinc sulfate and 350 g of sodium sulfite, with an effective component mass ratio of 3:2. The butyl xanthate consisted of 2 g of sodium ethyl xanthate and 3 g of sodium butyl xanthate, with an effective component mass ratio of 2:3. The amount of sodium carboxymethyl lignosulfonate added was on a dry basis, the effective component mass of zinc sulfate was calculated as ZnSO4, the effective component mass of sodium sulfite was calculated as Na2SO3, and the amounts of the other reagents were calculated based on their respective effective components.
[0206] Step M1 is exactly the same as in Example 1.
[0207] Step M2 is exactly the same as in Example 1.
[0208] M3. Add 75% of the total amount of sodium carboxymethyl lignosulfonate, i.e., 33.75 g / t of sodium carboxymethyl lignosulfonate from the raw ore, to the slurry obtained in step M2, and stir for 90 s.
[0209] M4. Add 105 g / t of raw ore HQ77 to the slurry obtained in step M3 and stir for 150 s.
[0210] M5. Add 10 g / t of No. 2 oil to the slurry obtained in step M4, stir for 45 s, and then aerate for roughing for 4 min to obtain roughing concentrate and roughing tailings.
[0211] M6. Add the remaining 25% of sodium carboxymethyl lignosulfonate, i.e., 11.25 g / t of sodium carboxymethyl lignosulfonate in the rough concentrate obtained in step M5, stir for 120 s and then finely concentrate for 3 min to obtain lead concentrate and finely concentrated tailings. Return the finely concentrated tailings to the roughing operation.
[0212] M7. Add 5 g / t of sodium ethyl xanthate from the raw ore to the roughing tailings obtained in step M5. The sodium ethyl xanthate consists of 2 g / t of sodium ethyl xanthate and 3 g / t of sodium butyl xanthate from the raw ore. Stir for 60 s and then scaveng for 8 min to obtain scavenged concentrate and flotation tailings. Return the scavenged concentrate to the roughing operation.
[0213] Structural characterization method of sodium carboxymethyl lignosulfonate
[0214] To characterize the effects of pre-fractionation and two-stage carboxymethylation on the functional group structure and molecular weight distribution of sodium lignosulfonate, the 5 kDa pre-fractionation cutoff obtained in step P2 and the carboxymethyl sodium lignosulfonate prepared in Example 1 were subjected to quantitative analysis of acidic groups; Fourier transform infrared spectroscopy was performed on the sodium lignosulfonate raw material, the 5 kDa pre-fractionation cutoff, and the carboxymethyl sodium lignosulfonate prepared in Example 1; and aqueous size exclusion chromatography was performed on the sodium lignosulfonate raw material, the carboxymethyl sodium lignosulfonate prepared in Example 1, and the single-stage carboxymethylated sodium lignosulfonate prepared in Comparative Example 3.
[0215] Determination of carboxyl and sulfonic acid group content
[0216] Take the 5 kDa pre-fractionated retentate and sodium carboxymethyl lignin obtained in step P2, and calculate their dry weight based on the solid content of each sample. Pass the samples through a hydrogen-form strong acid cation exchange resin to convert sodium ions in lignin sulfonate to hydrogen ions. Collect the effluent and wash the resin with deionized water, then combine the effluent and washings. Take the equivalent of 0.2000 g of the treated sample (dry weight), add deionized water to a final volume of 100 mL, and stir for 30 min at 25°C under nitrogen protection.
[0217] Conductivity-potential titration was performed using a standardized 0.0500 mol / L sodium hydroxide standard solution. 0.10 mL of sodium hydroxide standard solution was added each time, and data were recorded after the conductivity and pH readings stabilized. The first and second titration endpoints were determined by the intersection of adjacent linear segments in the conductivity-sodium hydroxide addition volume curve. The first titration endpoint corresponds to the volume of sodium hydroxide consumed by the sulfonic acid groups, and the volume difference between the first and second titration endpoints corresponds to the volume of sodium hydroxide consumed by the carboxyl groups.
[0218] The sulfonic acid group content is calculated according to the following formula:
[0219]
[0220] The carboxyl content is calculated using the following formula:
[0221]
[0222] In the formula, This represents the sulfonic acid content, expressed in mmol / g dry basis. Carboxyl content, expressed in mmol / g dry basis; This represents the concentration of the sodium hydroxide standard solution, in mol / L. The volume of the sodium hydroxide standard solution corresponding to the first titration endpoint is expressed in mL. This represents the total volume of the sodium hydroxide standard solution corresponding to the second titration endpoint, in mL. The dry weight of the sample is expressed in grams.
[0223] The carboxyl increment of sodium carboxymethyl lignin is calculated using the following formula:
[0224]
[0225] In the formula, The carboxyl group increment of sodium carboxymethyl lignin relative to the 5 kDa prefractionated cutoff is expressed in mmol / g dry basis. The content of carboxyl groups in sodium carboxymethyl lignosulfonate is expressed in mmol / g dry basis. The carboxyl content of the 5 kDa prefractionated filtrate is expressed in mmol / g dry basis.
[0226] The molar ratio of carboxyl group increment to sulfonic acid group content is calculated according to the following formula:
[0227]
[0228] In the formula, This represents the molar ratio of the increase in carboxyl groups to the content of sulfonic acid groups.
[0229] Fourier transform infrared spectroscopy analysis
[0230] Sodium lignosulfonate raw material and 5 kDa pre-fractionated retentate were prepared into aqueous solutions with solid content similar to that of sodium carboxymethyl lignosulfonate. Each group of samples was pre-frozen at -20℃ for 12 h, and then freeze-dried for 24 h under conditions where the cold trap temperature did not exceed -50℃ and the absolute pressure did not exceed 100 Pa. The resulting solids were further dried under vacuum at 40℃ for 6 h, ground, and passed through a 100-mesh sieve to obtain samples for infrared spectroscopy testing.
[0231] The detection was performed using a Fourier transform infrared spectrometer equipped with a diamond attenuated total internal reflection accessory, with a scanning range of 4000–600 cm⁻¹. -1 The resolution is 4 cm. -1 The number of scans was 32. Air background data was collected before each test, and all samples were tested under the same compression and scanning conditions. (The measurement was taken at 1510 cm⁻¹.) -1 The nearby lignin aromatic ring skeleton vibration absorption band is used as an internal reference peak to relatively correct the absorption intensity of each spectrum, so as to reduce the influence of sample amount and sample-crystal contact state on peak intensity.
[0232] Aqueous phase size exclusion chromatography analysis
[0233] Sodium lignosulfonate raw material, single-stage carboxymethylated sodium lignosulfonate prepared in Comparative Example 3, and carboxymethyl sodium lignosulfonate prepared in Example 1 were each prepared into a 2.0 mg / mL test solution based on dry weight. The test solutions were stirred at 25 °C for 2 h and then filtered through a hydrophilic filter membrane with a pore size of 0.45 μm.
[0234] Aqueous size exclusion chromatography equipped with a differential refractive index detector was used for detection. The chromatographic column was a hydrophilic gel-packed column suitable for the separation of water-soluble polymers, covering a separation range of 300–100,000 Da. The mobile phase was 0.10 mol / L sodium nitrate aqueous solution, the flow rate was 0.60 mL / min, the column temperature was 30℃, the differential refractive index detector temperature was 35℃, and the injection volume was 50 μL.
[0235] Calibration curves were established using narrow-distribution sodium polystyrene sulfonate standards with different molecular weights to determine the retention time versus the logarithm of molecular weight. Based on these calibration curves, the retention time corresponding to an apparent molecular weight of 3000 Da was determined. The molecular weight described in this specification for aqueous size exclusion chromatography is the apparent molecular weight obtained relative to the sodium polystyrene sulfonate standards.
[0236] Using all polymer response peaks appearing before the solvent peak as the integration range, the area of polymer response peaks after the retention time corresponding to 3000 Da is recorded as the low molecular weight component peak area, and the area of all polymer response peaks is recorded as the total peak area. The percentage of chromatographic peak area with a molecular weight less than 3000 Da is calculated according to the following formula:
[0237]
[0238] In the formula, The percentage of chromatographic peak area for molecules with a molecular weight less than 3000 Da, expressed in % . The chromatographic peak area in the region with a molecular weight less than 3000 Da; This represents the peak area of the total polymer response.
[0239] Figure 1 Fourier transform infrared spectra of sodium lignosulfonate raw material, 5 kDa pre-fractionated residue, and carboxymethyl sodium lignosulfonate prepared in Example 1. Curve a represents sodium lignosulfonate raw material, curve b represents the 5 kDa pre-fractionated residue, and curve c represents carboxymethyl sodium lignosulfonate prepared in Example 1. For ease of comparison, the curves for each sample have been shifted along the vertical axis; the vertical position does not represent the absolute absorbance difference between different samples.
[0240] Sodium lignosulfonate feedstock and 5 kDa pre-fractionation cutoff are both around 3400 cm⁻¹ -1 A broad absorption band of hydroxyl stretching vibration appears at approximately 2930 cm⁻¹. -1 An aliphatic carbon-hydrogen bond stretching vibration absorption band appears at approximately 1510 cm⁻¹. -1 A lignin aromatic ring skeletal vibrational absorption band appears at approximately 1040 cm⁻¹. -1 A sulfonic acid group-related absorption band appeared at the 5 kDa pre-fractionation residue. The main absorption peak positions of the 5 kDa pre-fractionation residue and the sodium lignosulfonate feedstock corresponded to each other, and no new characteristic absorption bands appeared, indicating that the 5 kDa ultrafiltration pre-fractionation did not change the basic structure of the lignin aromatic skeleton and sulfonic acid groups.
[0241] The carboxymethyl lignosulfonate prepared in Example 1 was heated to approximately 1600 cm⁻¹. -1 and 1415 cm -1 The absorption band at 1510 cm⁻¹ is relative to the absorption band at 1510 cm⁻¹. -1 The aromatic ring backbone absorption band is enhanced. Specifically, approximately 1600 cm⁻¹-1 The absorption band at approximately 1415 cm⁻¹ comprises the superposition of absorptions from the asymmetric stretching vibrations of the carboxylate group and the vibrations of the lignin aromatic skeleton. -1 The absorption band at this point corresponds to the symmetric stretching vibration of the carboxylate group. Approximately 2930 cm⁻¹ -1 The enhancement of the aliphatic C-H bond absorption band corresponds to the introduction of methylene groups in the carboxymethyl structure.
[0242] Carboxymethyl lignosulfonate at approximately 1040 cm -1 The presence of sulfonic acid group-related absorption bands indicates that the two-stage carboxymethylation introduces a carboxymethyl structure into the lignin sulfonate component while retaining the original sulfonic acid groups. The carboxyl group constitutes a coordinating group that binds to metal sites on the mineral surface, while the sulfonic acid group maintains the ionization, hydration, and extension states of the polymer chain segments in the aqueous phase, resulting in carboxymethyl sodium lignin forming a water-soluble polymer structure containing both carboxyl and sulfonic acid groups.
[0243] Figure 2 This is an aqueous size exclusion chromatogram of sodium lignosulfonate raw material, single-stage carboxymethylated sodium lignosulfonate prepared in Comparative Example 3, and carboxymethyl sodium lignosulfonate prepared in Example 1. Curve a represents sodium lignosulfonate raw material, curve b represents single-stage carboxymethylated sodium lignosulfonate prepared in Comparative Example 3, and curve c represents carboxymethyl sodium lignosulfonate prepared in Example 1. For ease of comparison, the curves for each sample are shifted along the vertical axis; the vertical position does not represent the absolute difference in refractive response between different samples. The upper horizontal axis in the figure represents the apparent molecular weight determined relative to the sodium polystyrene sulfonate standard. The vertical dashed line represents the retention time corresponding to an apparent molecular weight of 3000 Da, and the region to the right of the vertical dashed line represents the response region of polymers with an apparent molecular weight less than 3000 Da.
[0244] The chromatogram of sodium lignin sulfonate raw material showed a low-molecular-weight response peak after the high-molecular-weight response peak, indicating that the raw material contains high-molecular-weight lignin sulfonates, oligomeric lignin sulfonates, and other low-molecular-weight water-soluble organic components. Comparative Example 3, without 5 kDa ultrafiltration pre-fractionation and 3 kDa ultrafiltration washing, still retained low-molecular-weight chromatographic peaks in the region below 3000 Da for its single-stage carboxymethylation product, indicating that single-stage carboxymethylation did not remove the low-molecular-weight lignin components and low-molecular-weight byproducts formed in the reaction from the raw material.
[0245] The main response peak of the carboxymethyl lignin sodium prepared in Example 1 is concentrated towards shorter retention times, indicating that the apparent hydrodynamic volume of this sample is mainly distributed in the higher apparent molecular weight range. The peak area of this sample decreases in the region below 3000 Da, and the percentage of the peak area with a molecular weight less than 3000 Da in the total polymer response peak area is no greater than 3%, which meets the structural constraint that this parameter in carboxymethyl lignin sodium should not exceed 5%.
[0246] The 5 kDa ultrafiltration pre-classification first removes some low-molecular-weight components from the sodium lignosulfonate feedstock, ensuring that subsequent alkalization and carboxymethylation reactions mainly occur on the high-molecular-weight retained components. Sodium chloroacetate is added in two stages, allowing the reactant concentration, reaction temperature, and system alkalinity to be controlled separately according to different reaction stages, reducing hydrolysis consumption caused by excessively high local sodium chloroacetate concentrations. After the reaction is complete, the 3 kDa ultrafiltration washing further removes unreacted sodium chloroacetate, glycolate, neutralizing salts, and low-molecular-weight reaction products, concentrating the molecular weight distribution of carboxymethyl lignosulfonate in the high-molecular-weight region and reducing the entry of low-molecular-weight components into the flotation slurry phase.
[0247] To verify the technical effect of the present invention, lead-zinc-gold-silver sulfide ore from the same batch was selected. After crushing, mixing, and fractionation, seven groups of raw ore samples with the same dry basis mass were prepared, and the contents of Pb, Zn, S, Au, and Ag were determined from the raw ore samples. Each group of raw ore samples was treated according to the reagent formulations, grinding fineness, pulp concentration, pulp pH, reagent addition sequence, and roughing, cleaning, and scavenging processes described in Examples 1, 2, 3, 1, 2, 3, and 4.
[0248] The seven flotation tests were numbered sequentially from DJK1001 to DJK1007. The lead concentrate obtained from each test was labeled with the letter C after the corresponding number, and the final flotation tailings obtained from each test were labeled with the letter T after the corresponding number. For example, the lead concentrate and flotation tailings obtained in Example 1 were numbered DJK1001-C and DJK1001-T, respectively.
[0249] The lead concentrate and flotation tailings obtained from each group were dehydrated, dried, and weighed, and the dry basis mass of the lead concentrate and flotation tailings was recorded. The same type of flotation products from the same group were thoroughly mixed and reduced to prepare corresponding chemical analysis samples. If the amount of product obtained from a single flotation was insufficient to meet the sampling requirements for precious metal analysis, parallel flotation was performed using the same raw ore, the same reagent system, and the same flotation conditions. The same type of products obtained from the same group were combined, mixed, and then sampled.
[0250] The yields of lead concentrate and flotation tailings are calculated using the following formula:
[0251]
[0252] In the formula, For flotation products Yield, in percentages of % For flotation products Dry basis mass, in grams; The dry basis mass of the corresponding group of raw ore is expressed in grams. It is either C or T, where C represents lead concentrate and T represents flotation tailings.
[0253] The recovery rates of each element in lead concentrate or flotation tailings are calculated using the following formula:
[0254]
[0255] In the formula, For elements Entering flotation products Recovery rate, in % It can be Pb, Zn, S, Au, or Ag; For flotation products Middle elements The content; Elements in the raw ore The content of Pb, Zn, and S is expressed as mass fraction, while the content of Au and Ag is expressed as g / t. The same element is expressed in the same unit of content in both the numerator and denominator.
[0256] When lead concentrate and flotation tailings constitute the final flotation product, the recovery rates of each element are balanced according to the following formula:
[0257]
[0258] In the formula, For elements The recovery balance value, expressed as a percentage. This value is used to verify the consistency between the results of flotation product weighing, sampling, and chemical analysis.
[0259] 1. Pb grade and Pb recovery rate
[0260] The Pb content in each group of lead concentrates was determined according to GB / T 8152.2-2006 "Chemical Analysis Methods for Lead Concentrates - Determination of Lead Content - Lead Sulfate Precipitation-EDTA Back Titration Method". The Pb content in the raw ore and flotation tailings was determined according to GB / T 14353.2-2010 "Chemical Analysis Methods for Copper, Lead and Zinc Ores - Part 2: Determination of Lead Content" using flame atomic absorption spectrophotometry.
[0261] The raw ore, lead concentrate, and flotation tailings were dried, mixed, and ground to a particle size of less than 0.074 mm. A representative laboratory sample of no less than 100 g was taken for each sample. The sample was weighed according to the determination range specified in the corresponding standard and two parallel determinations were performed.
[0262] The equipment used for determining the Pb content in lead concentrate includes an analytical balance with a sensitivity of 0.1 mg, a hot plate, a glass filter, and a standard burette. After acid decomposition, lead sulfate precipitate forms on the sample. The precipitate is separated and dissolved, and excess EDTA standard solution is added, followed by back titration with the corresponding metal standard titration solution. The Pb content of the raw ore and flotation tailings is determined using a flame atomic absorption spectrophotometer after acid decomposition and volume adjustment.
[0263] Pb grade is expressed as a mass fraction, in percentage (%). The Pb grade in lead concentrate reflects the enrichment of lead in the froth product; the Pb recovery rate into lead concentrate reflects the proportion of lead in the raw ore that enters the final lead concentrate; and the Pb recovery rate into flotation tailings reflects the proportion of lead lost in the final tailings. Pb grade and Pb recovery rate should be evaluated together; Pb grade should not be compared alone at the cost of significantly reducing Pb recovery rate.
[0264] 2. Zn grade and Zn recovery rate
[0265] The Zn content in each group of lead concentrate was determined according to GB / T 8152.4-2006 "Chemical Analysis Methods for Lead Concentrate - Determination of Zinc Content - EDTA Titration Method". The Zn content in the raw ore and flotation tailings was determined according to GB / T 14353.3-2010 "Chemical Analysis Methods for Copper, Lead and Zinc Ores - Part 3: Determination of Zinc Content" using flame atomic absorption spectrophotometry.
[0266] Dry, mix, and grind each sample until the particle size is less than 0.074 mm. Take a representative laboratory sample of no less than 100 g for each sample, weigh the sample according to the determination range specified in the corresponding standard, and perform two parallel determinations.
[0267] The equipment used for determining the Zn content in lead concentrate includes an analytical balance with a sensitivity of 0.1 mg, a hot plate, a separation device, and a standard burette. After acid decomposition and separation of interfering elements, the Zn content is determined using a standard EDTA titration solution. The Zn content in the raw ore and flotation tailings is determined using a flame atomic absorption spectrophotometer after acid decomposition and volume adjustment.
[0268] Zn grade is expressed as a mass fraction, in percent. Lower Zn grades in lead concentrate and lower Zn recovery rates in lead concentrate indicate a smaller proportion of sphalerite entering the lead concentrate; higher Zn recovery rates in flotation tailings indicate a higher degree of separation between zinc and lead minerals. Zn indicators should be compared under the condition that Pb recovery rates in each group are at similar levels.
[0269] 3. S grade and S recovery rate
[0270] The sulfur content in raw ore, lead concentrate and flotation tailings was determined by the barium sulfate gravimetric method as specified in GB / T 14353.12-2010 "Chemical Analysis Methods for Copper, Lead and Zinc Ores - Part 12: Determination of Sulfur Content".
[0271] Each sample was dried, mixed, and ground until the particle size was less than 0.074 mm. A representative laboratory sample of at least 100 g was retained for each sample. The sample was weighed according to the standard specifications based on its sulfur content, and two parallel determinations were performed. The testing equipment included an analytical balance with a sensitivity of 0.1 mg, a hot plate, a glass filter, a porcelain crucible, and a high-temperature furnace. After decomposition and oxidation, the sulfur in the sample was converted to sulfate ions, which then formed barium sulfate precipitate. After aging, filtration, washing, ignition, and weighing, the sulfur content was calculated.
[0272] S grade is expressed as a mass fraction, in percentages (%). Galena itself contains sulfur, so the S grade in lead concentrate cannot be directly equated with the pyrite content in the lead concentrate. Under similar Pb grades and recoveries, a lower S grade and S recovery rate in lead concentrate indicates a lower proportion of pyrite and other non-lead sulfide minerals entering the lead concentrate. The S recovery rate in flotation tailings reflects the distribution of iron sulfide minerals and other sulfur-containing minerals in the tailings and should be evaluated in conjunction with Pb and Zn recovery rates.
[0273] 4. Au and Ag grades and recovery rates
[0274] The Au and Ag contents in each group of lead concentrates were determined according to GB / T 8152.10-2006 "Chemical Analysis Methods for Lead Concentrates - Determination of Silver and Gold Contents - Lead Precipitation or Ash Blowing Test and Flame Atomic Absorption Spectrometry". The Au content in the raw ore and flotation tailings was determined according to GB / T 20899.1-2019 "Chemical Analysis Methods for Gold Ore - Part 1: Determination of Gold Content", and the Ag content in the raw ore and flotation tailings was determined according to GB / T20899.2-2019 "Chemical Analysis Methods for Gold Ore - Part 2: Determination of Silver Content - Flame Atomic Absorption Spectrometry".
[0275] Considering the uniformity of Au and Ag distribution in the ore samples, representative laboratory samples of no less than 500 g were prepared for each type of raw ore and flotation product. After drying, homogenization, and reduction, the samples were ground to a particle size of less than 0.074 mm. The samples were then weighed according to the determination range specified in the relevant standards and subjected to two parallel determinations. The testing equipment included an analytical balance with a sensitivity of 0.1 mg or higher, a fire assay furnace, an ash blowing furnace, ash pans, and a flame atomic absorption spectrometer.
[0276] Lead concentrate samples were subjected to lead precipitation or ash blowing assay according to GB / T 8152.10-2006 to allow Au and Ag to enter the precious metal aggregates. After separation and dissolution, the results were determined by flame atomic absorption spectrometry. Au in the raw ore and flotation tailings was enriched, separated, and determined by instrumental analysis according to GB / T 20899.1-2019; Ag in the raw ore and flotation tailings was decomposed, diluted to volume, and determined by flame atomic absorption spectrometry according to GB / T20899.2-2019.
[0277] Au and Ag grades are expressed in g / t. Higher Au and Ag recovery rates in lead concentrate indicate a higher proportion of associated gold and silver entering the concentrate; lower recovery rates in flotation tailings indicate a smaller loss of gold and silver in the final tailings. Some gold and silver may be distributed in pyrite or other carrier minerals; therefore, Au and Ag grades and recoveries should be evaluated in conjunction with Pb, Zn, and S grades and recoveries.
[0278]
[0279] The test results of lead concentrate and final tailings show that the yield of lead concentrate in each group is 4.47%–5.17%, and the yield of final tailings is 94.83%–95.53%. The sum of the recoveries of Pb, Zn, S, Au, and Ag in each group of lead concentrate and final tailings is 100%, maintaining a quality balance between yield, grade, and recovery. This allows for comparison of the effects of different reagent compositions, carboxymethyl lignosulfonate structure, and reagent addition sequence on lead-zinc separation.
[0280] Comparative Example 1 used a lime, zinc sulfate, and No. 25 black reagent system, with a lead concentrate Pb grade of 60.29%, a Zn grade of 6.14%, a Pb recovery rate of 94.09%, and a Zn recovery rate of 7.68% in the lead concentrate. Comparative Example 2 used a low-alkali lead flotation reagent system of HQD82 and HQ77, with a lead concentrate Pb grade of 66.25%, a Zn grade of 4.05%, a Pb recovery rate of 94.37%, and a Zn recovery rate of 4.62% in the lead concentrate. Compared to Comparative Example 1, Comparative Example 2 showed a 5.96 percentage point increase in Pb grade, a 2.09 percentage point decrease in Zn grade, a 3.06 percentage point decrease in Zn recovery rate in the lead concentrate, and changes in Pb and Ag recovery rates of 0.28 and 0.14 percentage points, respectively. Correspondingly, the Zn recovery rate in the final tailings of Comparative Example 2 increased from 92.32% to 95.38%. The above results indicate that the HQD82 and HQ77 low-alkali reagent regimes reduce the proportion of sphalerite entering the lead concentrate while maintaining the recovery levels of galena and associated silver components, and can be used as a base reagent regime before the addition of carboxymethyl lignosulfonate.
[0281] Example 1, based on Comparative Example 2, added sodium carboxymethyl lignin with a carboxyl group increment of 0.60 mmol / g dry basis and a sulfonic acid group content of 1.60 mmol / g dry basis, and added in the order of HQD82, HQ77, and sodium carboxymethyl lignin. The resulting lead concentrate had a Pb grade of 68.40%, a Zn grade of 2.93%, and a S grade of 16.80%, with a Pb recovery rate of 94.00%. The Zn and S recoveries in the lead concentrate were 3.23% and 4.06%, respectively. Compared with Comparative Example 2, Example 1 showed a 2.15 percentage point increase in Pb grade, and a 1.12 percentage point and 2.20 percentage point decrease in Zn and S grades, respectively. The Zn recovery rate in the lead concentrate decreased from 4.62% to 3.23%, a relative decrease of 30.09%; the S recovery rate in the lead concentrate decreased from 4.76% to 4.06%, a relative decrease of 14.71%. In Example 1, the Pb recovery rate decreased by only 0.37 percentage points, the Au recovery rate increased by 0.57 percentage points, and the Ag recovery rate decreased by 0.67 percentage points.
[0282] In Example 1, the Pb grade in the final tailings was 0.21%, with a Pb recovery rate of 6.00%. The Zn and S recovery rates in the final tailings were 96.77% and 95.94%, respectively. Compared to Comparative Example 2, the Zn recovery rate in the final tailings of Example 1 increased by 1.39 percentage points, the S recovery rate increased by 0.70 percentage points, while the Pb recovery rate in the tailings only increased by 0.37 percentage points. The data from both the concentrate and tailings indicate that after adding sodium carboxymethyl lignosulfonate, the reduced Zn and S were mainly transferred to the final tailings, without a corresponding loss of Pb.
[0283] In Example 1, HQ77 first contacts the slurry and forms a collector adsorption layer on the galena surface. Subsequently, sodium carboxymethyl lignin is added, primarily contacting the still hydrophilic surfaces of sphalerite and pyrite. The carboxyl groups in sodium carboxymethyl lignin form multi-site coordination with zinc, iron, and their hydroxylation sites on the sphalerite and pyrite surfaces. The sulfonic acid groups maintain the hydration and extension of the polymer chains in the slurry, forming a hydrous adsorption layer and a steric hindrance layer at the mineral solid-liquid interface. This interface structure reduces the adhesion ratio of sphalerite and pyrite to bubbles, allowing more Zn and S to remain in the final tailings. HQ77 pre-occupies collecting sites on the galena surface, limiting the direct adsorption of sodium carboxymethyl lignin on the galena surface; therefore, the recovery rates of Pb, Au, and Ag remain within a range close to that of the basic reagent regime.
[0284] Example 2 uses the lower limit combination of carboxymethyl lignosulfonate structural parameters, reagent dosage, and flotation process parameters. Its lead concentrate has a Pb grade of 66.90%, a Zn grade of 3.54%, and a S grade of 17.70%, with a Pb recovery rate of 94.20%. The Zn and S recoveries into the lead concentrate are 3.99% and 4.38%, respectively. Compared to Comparative Example 2, the Pb recovery rate in Example 2 differs by 0.17 percentage points, the Zn recovery rate into the lead concentrate decreases by 0.63 percentage points, and the S recovery rate into the lead concentrate decreases by 0.38 percentage points. The lower carboxyl group increment and the 30 g / t carboxymethyl lignosulfonate dosage can form an adsorption layer at the sphalerite and pyrite interface, but the polymer coverage ratio on the mineral surface is lower than in Example 1. Therefore, its zinc and sulfur inhibition indices are between those of Example 1 and Comparative Example 2.
[0285] Example 3 uses the upper limit combination of carboxymethyl lignosulfonate (CML) structural parameters, reagent dosage, and flotation process parameters. Its lead concentrate Pb grade reaches 69.00%, Zn grade is 2.77%, and S grade is 16.10%. The Zn and S recoveries into the lead concentrate are 3.00% and 3.82%, respectively, the lowest among the three examples. The Pb recovery rate in Example 3 is 93.10%, 0.90 percentage points lower than in Example 1; the Ag recovery rate is 71.80%, 1.00 percentage point lower than in Example 1. The higher carboxyl group increment and 60 g / t CML dosage in Example 3 increase the adsorption coverage of sphalerite and pyrite surfaces, while also increasing the probability of CML contacting the surface of galena partially not completely covered by HQ77. This results in a further reduction in Zn and S entrainment, and a corresponding decrease in Pb and Ag recovery rates. Example 1 falls between Examples 2 and 3, forming a relatively balanced parameter combination in terms of Pb recovery, Zn entrainment, and S entrainment.
[0286] Comparative Example 3 used carboxymethylated sodium lignin sulfonate that had not undergone 5 kDa pre-classification, single-stage carboxymethylation, and had not been washed with 3 kDa post-filtration. Its lead concentrate had a Pb grade of 66.80%, a Zn grade of 3.48%, and a S grade of 17.40%, with a Pb recovery rate of 92.70% and a Zn recovery rate of 3.87% in the lead concentrate. Compared to Example 1, Comparative Example 3 showed a 1.60 percentage point decrease in Pb grade and a 1.30 percentage point decrease in Pb recovery rate, a 0.55 percentage point increase in Zn grade and a 0.64 percentage point increase in Zn recovery rate in the lead concentrate, and decreases in Au and Ag recovery rates by 1.80 and 1.60 percentage points, respectively. The final Pb grade in the tailings of Comparative Example 3 was 0.25%, higher than the 0.21% in Example 1, and the Pb recovery rate in the tailings increased from 6.00% to 7.30%.
[0287] Aqueous size exclusion chromatography results showed that the carboxymethylated sodium lignin sulfonate in Comparative Example 3 contained a significant amount of low-molecular-weight components. These components exhibited rapid solution-phase diffusion rates, readily contacting soluble metal ions in the slurry and non-selective sites on the mineral surface; however, the number of adsorption sites and spatial coverage provided by a single molecule was limited. In Example 1, pre-fractionation at 5 kDa ensured that carboxymethylation primarily occurred on the high-molecular-weight cutoff components, followed by 3 kDa elution to remove low-molecular-weight reactants and byproducts, concentrating carboxyl groups within the lignin sulfonate segments with a large hydrodynamic volume. This structure improved the coverage and adsorption stability of each adsorbed molecule on the mineral surface, reduced solution-phase consumption of low-molecular-weight components, and simultaneously maintained Pb recovery while reducing Zn entrainment compared to Comparative Example 3.
[0288] The reagent composition and dosage of Comparative Example 4 were the same as in Example 1, but the order of addition was adjusted to HQD82, sodium carboxymethyl lignosulfonate, and HQ77. Its lead concentrate had a Zn grade of 3.13% and a S grade of 16.80%, with Zn and S recoveries of 3.39% and 3.99% respectively, close to that of Example 1. Its Pb recovery rate was 90.90%, Au recovery rate was 27.60%, and Ag recovery rate was 69.80%, representing decreases of 3.10, 3.90, and 3.00 percentage points compared to Example 1, respectively. The Pb grade in the final tailings of Comparative Example 4 was 0.32%, the highest among the seven sets of tests, with a Pb recovery rate of 9.10% in the tailings.
[0289] In Comparative Example 4, when sodium carboxymethyl lignosulfonate was added first, the HQ77 collector adsorption layer had not yet formed on the galena surface. Sodium carboxymethyl lignosulfonate could bind to lead sites on the galena surface through its carboxyl groups, causing part of the galena surface to become hydrated. Subsequent addition of HQ77 could not completely replace the already adsorbed polymer segments, leading to an increase in the proportion of galena and its associated gold and silver minerals entering the final tailings. In Example 1, HQ77 was added first, followed by sodium carboxymethyl lignosulfonate, ensuring that collector adsorption and polymer interface regulation proceeded in the order of reactions on different mineral surfaces. Therefore, while reducing the proportion of Zn and S entering the lead concentrate, the losses of Pb, Au, and Ag were kept at a low level.
[0290] Based on combined lead concentrate and final tailings data, 5 kDa pre-classification, two-stage carboxymethylation, and 3 kDa post-washing jointly determined the functional group density and molecular weight composition of sodium carboxymethyl lignosulfonate (CML). The order of polymer contact with the surfaces of galena, sphalerite, and pyrite was determined by the prior addition of HQ77 and subsequent addition of CML. The staged addition of CML before roughing and cleaning ensured that the original mineral surfaces before roughing and the re-exposed mineral surfaces before cleaning were respectively covered with polymers. These structural parameters and dosing steps collectively correspond to changes in lead concentrate Pb grade, Zn and S entrainment amounts, and Pb, Au, and Ag recoveries.
[0291] The foregoing description of the specifications and embodiments is intended to explain the scope of protection of this invention, but does not constitute a limitation on the scope of protection of this invention. Modifications, equivalent substitutions, or other improvements to the embodiments of this invention or a portion thereof that can be obtained by those skilled in the art through logical analysis, reasoning, or limited experimentation, based on the teachings of this invention or the foregoing embodiments, in conjunction with common knowledge, general technical knowledge, and / or existing technology, should all be included within the scope of protection of this invention.
Claims
1. A flotation reagent composition for low-alkali conditions, characterized in that, This includes individually packaged sodium carboxymethyl lignin, zinc salt-sulfite complexes, dialkyl dithiophosphates, terpene alcohol mixtures, and ethyl xanthate-butyl xanthate complexes; Based on 100 parts by weight of sodium carboxymethyl lignin on a dry basis, the active ingredient comprises: 100 parts sodium carboxymethyl lignin, 1250-3340 parts of a zinc salt-sulfite complex, 125-385 parts of dialkyl dithiophosphate, 13-40 parts of a terpene alcohol mixture, and 6-34 parts of an ethyl xanthate-butyl xanthate complex; the zinc salt-sulfite complex has a zinc salt to sulfite mass ratio of 1.0-2.0:1 based on the active ingredient mass, and the ethyl xanthate-butyl xanthate complex has an ethyl xanthate to butyl xanthate mass ratio of 1:1.0-2.0 based on the active ingredient mass. The sodium carboxymethyl lignin is a pre-fractionated two-stage carboxymethylated lignin sulfonate sodium, prepared according to the following steps: P1. Add sodium lignosulfonate to water to prepare an aqueous solution of sodium lignosulfonate, stir and then filter. P2, the sodium lignosulfonate aqueous solution obtained in step P1 is washed and concentrated through an ultrafiltration membrane with a nominal molecular weight cutoff of 5 kDa, and the retentate is collected; P3, add the first portion of sodium hydroxide to the retentate obtained in step P2 for alkalization treatment; P4. Add 65-75% of the total amount of sodium chloroacetate to the material obtained in step P3 to carry out the first stage of carboxymethylation reaction. P5. Heat the material obtained in step P4, add the remaining 25-35% sodium chloroacetate and the second part of sodium hydroxide dropwise to carry out the second stage of carboxymethylation reaction. P6. Cool the reaction solution obtained in step P5, add hydrochloric acid to adjust the pH, wash and filter it through an ultrafiltration membrane with a nominal molecular weight cutoff of 3 kDa, and collect the retentate. P7. Concentrate the retentate obtained in step P6 to obtain the carboxymethyl lignosulfonate.
2. The flotation reagent composition under low-alkali conditions according to claim 1, characterized in that, The zinc salt-sulfite complex is composed of zinc sulfate and sodium sulfite, wherein the mass ratio of zinc sulfate to sodium sulfite based on the effective ingredient mass is 3:2, the effective ingredient mass of zinc sulfate is ZnSO4, and the effective ingredient mass of sodium sulfite is Na2SO3; the dialkyl dithiophosphate is selected from at least one of diethyl dithiophosphate, dipropyl dithiophosphate, diisopropyl dithiophosphate, dibutyl dithiophosphate, and diisobutyl dithiophosphate; the terpene alcohol mixture includes terpineol; the ethyl xanthate-butyl xanthate complex is composed of ethyl xanthate alkali metal salt and butyl xanthate alkali metal salt, wherein the mass ratio of ethyl xanthate alkali metal salt to butyl xanthate alkali metal salt based on the effective ingredient mass is 2:
3.
3. The flotation reagent composition under low-alkali conditions according to claim 1, characterized in that, Based on 100 parts by weight of the sodium lignosulfonate residue obtained in step P2 (dry basis), the raw materials for preparing the carboxymethyl lignosulfonate include: 100 parts of sodium lignosulfonate residue, 32-44 parts of sodium chloroacetate, 11.8-17.9 parts of sodium hydroxide, and 550-750 parts of water for reaction preparation. The washing and filtration water in steps P2 and P6 is calculated separately. The amount of hydrochloric acid added is the amount used to adjust the pH of the reaction solution obtained in step P5 to 7.8-8.
3.
4. The flotation reagent composition under low-alkali conditions according to claim 3, characterized in that, In step P1, the solid content of the sodium lignosulfonate aqueous solution is 12–18 wt%, the stirring temperature is 25–35℃, and the stirring time is 30–60 min. In step P2, the ultrafiltration temperature is 25–35℃, the transmembrane pressure difference is 0.15–0.30 MPa, the volume of washing water is 3–4 times the initial volume of the retentate, and the solid content of the resulting retentate is 15–20 wt%. In step P3, the alkalization temperature is 30–34℃, the pH is 11.8–12.2, and the alkalization time is 20–40 min. In step P4, the sodium chloroacetate is added dropwise over a time of 60–90 min, the reaction temperature is 36–40℃, the pH is 11.6–12.0, and the reaction time after the addition is 30–45 min. In step P5, the heating rate is 0.2–0.5℃ / min, and the sodium chloroacetate is added dropwise over a time of 30–60 min. The reaction time is 46–50℃, pH is 11.1–11.5, reaction time after addition is 2–3 h, and the molar ratio of sodium hydroxide to sodium chloroacetate is 1.08–1.18:
1. In step P6, the cooling temperature is not higher than 30℃, the ultrafiltration temperature is 25–35℃, the transmembrane pressure difference is 0.15–0.30 MPa, and the volume of washing water is 4–6 times the initial volume of the retentate.
5. The flotation reagent composition under low-alkali conditions according to claim 4, characterized in that, Based on 100 parts by weight of the sodium lignosulfonate residue obtained in step P2 (dry basis), the amount of sodium chloroacetate added is 38 parts, and the amount of sodium hydroxide added is 14.75 parts; 70% of the total amount of sodium chloroacetate is added in step P4, and the remaining 30% of sodium chloroacetate is added in step P5; the molar ratio of sodium hydroxide to sodium chloroacetate is 1.13:
1.
6. The flotation reagent composition under low-alkali conditions according to claim 1, characterized in that, The carboxylmethyl lignin sodium has a carboxyl group increment of 0.50–0.70 mmol / g dry basis relative to the sodium lignin sulfonate retentate obtained in step P2, and a sulfonic acid group content of 1.40–1.80 mmol / g dry basis. The molar ratio of the carboxyl group increment to the sulfonic acid group content is 0.30–0.45:
1. In the aqueous volume exclusion chromatogram of the carboxylmethyl lignin sodium, the percentage of the chromatographic peak area with a molecular weight less than 3000 Da is no more than 5% of the total chromatographic peak area. The solid content of the carboxylmethyl lignin sodium is 18–22 wt%, and the pH is 7.8–8.
3.
7. The flotation reagent composition under low-alkali conditions according to claim 6, characterized in that, Based on 100 parts by weight of sodium carboxymethyl lignin on a dry basis, the active ingredients include: 100 parts of sodium carboxymethyl lignin, 1660-2500 parts of zinc salt-sulfite complex, 190-250 parts of dialkyl dithiophosphate, 20-27 parts of terpene alcohol mixture, and 11-17 parts of ethyl xanthate-butyl xanthate complex.
8. The application of a flotation reagent composition under low-alkali conditions as described in any one of claims 1 to 7, characterized in that, The flotation reagent composition comprises independently formulated sodium carboxymethyl lignin, a zinc salt-sulfite complex, a dialkyl dithiophosphate, a terpene alcohol mixture, and an ethyl xanthate-butyl xanthate complex. The zinc salt-sulfite complex consists of zinc sulfate and sodium sulfite, with a mass ratio of zinc sulfate to sodium sulfite of 1.0–2.0:1 based on the effective components. The ethyl xanthate-butyl xanthate complex consists of ethyl xanthate alkali metal salt and butyl xanthate alkali metal salt, with a mass ratio of ethyl xanthate alkali metal salt to butyl xanthate alkali metal salt of 1:1.0–2.0 based on the effective components. The sodium carboxymethyl lignin is a pre-fractionated two-stage carboxymethylated lignin sulfonate with a carboxyl group increment of 0.50–0.70 mmol / g dry basis and a sulfonic acid group content of 1.40–1.80%. The concentration is mmol / g dry basis, the molar ratio of carboxyl group increment to sulfonic acid group content is 0.30–0.45:1, and the percentage of peak area with molecular weight less than 3000 Da in the aqueous phase size exclusion chromatogram is no greater than 5% of the total peak area; the application includes the following steps: M1, grinding lead-zinc-gold-silver sulfide ore to obtain slurry for flotation; M2, add zinc salt-sulfite compound to the slurry to be flotated obtained in step M1, adjust the pH of the slurry to 7.8-8.8 and perform slurry conditioning; M3, add dihydrodithiophosphate to the slurry obtained in step M2 and stir; M4, add 70-80% of the total amount of sodium carboxymethyl lignosulfonate to the slurry obtained in step M3 and stir; M5, add a mixture of terpene alcohols to the slurry obtained in step M4, and perform aeration roughing to obtain roughing concentrate and roughing tailings respectively; M6. Add the remaining 20-30% of sodium carboxymethyl lignosulfonate to the rough concentrate obtained in step M5 for further refining to obtain lead concentrate and refined tailings. The refined tailings are then returned to the roughing operation. M7. Add ethyl xanthate-butyl xanthate complex to the roughing tailings obtained in step M5, perform scavenging to obtain scavenged concentrate and flotation tailings, and return the scavenged concentrate to the roughing operation.
9. The application according to claim 8, characterized in that, The total amount of carboxymethyl lignosulfonate added, on a dry basis, is 30–60 g / t of raw ore; the amount of zinc salt-sulfite compound added is 750–1000 g / t of raw ore; the amount of dialkyl dithiophosphate added is 75–115 g / t of raw ore; the amount of terpene alcohol mixture added is 8–12 g / t of raw ore; and the amount of ethyl xanthate-butyl xanthate compound added is 4–10 g / t of raw ore. Except for carboxymethyl lignosulfonate, the amounts of the other components added are based on the effective ingredients.
10. The application according to claim 8 or 9, characterized in that, In step M1, the grinding fineness is such that mineral particles with a diameter less than 0.074 mm account for 70-80% of the total mass of mineral particles, the slurry solids concentration is 35-42%, and the slurry temperature is 10-35℃; the slurry conditioning time in step M2 is 180 s; the stirring time in step M3 is 120-180 s; the stirring time in step M4 is 60-120 s; in step M5, the stirring time after adding the terpene alcohol mixture is 30-60 s, and the roughing time is 4 min; in step M6, the stirring time after adding carboxymethyl lignosulfonate is 90-150 s, and the cleaning time is 3 min; in step M7, the stirring time after adding the ethyl xanthate-butyl xanthate complex is 60 s, and the scavenging time is 8 min.